A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Atmospheric assessment of polychlorinated naphthalenes (PCNs) and polychlorinated biphenyls (PCBs) using pine needles in Detroit, Michigan - Sung-Hee Seo; Tian Xia; Adriana C. Torres-Moreno; Md Kamrul Islam; Stuart Batterman (Journal of Hazardous Materials, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Camizestrant-induced heart rate reduction is mediated via a sinoatrial node pacemaker channel mechanism - Andrew Hall; Saïd El-Haou; Inmaculada C. Villar; David Molla; Maggie Kwan; Stuart Purbrick; David Henry; Jason Kirk; Glen Hawthorne; Serena Canzolino; Joanna Harding; Alexander Harmer; et al. (Toxicology and Applied Pharmacology, 2026)

Gene Expression and Structural Differences Underpinning Black and White Colouration in Spiders - Fabian C. Salgado‐Roa; Devi Stuart‐Fox; Laura Ospina‐Rozo; Iliana Medina (Molecular Ecology, 2026)
The presence of multiple color variants within a single population, known as color polymorphism, is a striking example of intraspecific phenotypic variation and a model for studying evolutionary processes. These processes depend on the underlying mechanisms such as the genes and pigments involved; but we currently lack such information for non‐model groups such as arachnids. We examined the genes associated with color polymorphism in the Australian Christmas spider, Austracantha minax , a widespread species with two female‐restricted color morphs: one that is completely black and the other presenting a black‐and‐white pattern on its dorsum. We sequenced the mRNA of individuals of both morphs at different developmental stages and assessed differences in gene expression between color morphs based on a de novo transcriptome assembly for the species, and integrated this with high resolution electron microscopy observations. We found that gene expression patterns are primarily influenced by the stage of development, and within each stage we found differentially expressed genes between the black and black‐and‐white morphs, especially in the adult stage. Contrary to expectations, these genes were not associated with melanin or guanine crystal deposition (detected in the microscopy), but were associated with chitin and cuticle metabolic processes. By exploring arachnid coloration at the transcriptomic level, our work reveals for the first time genetic mechanisms underpinning the evolution of color polymorphism in spiders.

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Digital technologies and the study of adaptation in small-scale fisheries - Juan Carlos Villaseñor-Derbez; Rebeca Fernández; Stuart Fulton; Arturo Hernández-Velasco; Tamara Hernández; C. Brock Woodson; Juan Camilo Cárdenas; Giulio A. DeLeo; Jorge Torre; Fiorenza Micheli (Ocean & Coastal Management, 2026)

Limbic and whole-brain functional connectivity in non-substance abusers with human immunodeficiency virus (HIV) - Stuart D. Washington; Anisa Thomas; Kehinde Omisore; Cedric Cole; Tomilowo Abijo; Ashley VanMeter; Marjorie C. Gondré-Lewis (Journal of NeuroVirology, 2026)

Divergent demographic responses of boreal-breeding ducks to growing season variability - David J. Messmer; Stuart Slattery; Mark C. Drever; Chris Derksen; Robert G. Clark (Oecologia, 2026)
In seasonal environments climatic variability shapes the timing, duration, and magnitude of primary production with effects that may percolate upward through food chains. While the role of spring phenology and implications of trophic mismatches have been documented in some bird species, including waterfowl, there is little research on the role of growing season duration or overall productivity. Duck species breeding in the western boreal forest (WBF) of North America vary widely in their average timing and plasticity for breeding dates, which may set up differing sensitivity to spring phenology. In contrast, increases in growing season duration and productivity may positively impact species regardless of life history through the extension of the breeding season and bottom-up trophic enrichment. We tested these hypotheses using breeding population estimates for 8 species (or species groups) of ducks and normalized difference vegetation index to infer spring phenology, length of growing season, and growing season productivity for duck survey areas in the WBF, 1982–2019. Spring phenology had mixed effects on species’ population growth rates, and effects were generally not consistent with mediation by average breeding dates or plasticity. Length of season and productivity effects showed some species’ population growth rates decreasing following longer seasons or higher productivity, opposite our predictions. These results suggest that, for secondary consumers like ducks, the role of growing season characteristics may be mediated or superseded by more complex biotic and abiotic interactions than can be explained with simple annual summaries of growing season characteristics.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Missing or Mis‐Telling the Story? Trade‐Offs for Restriction‐Site Associated Compared to Whole Genome Sequencing - Kamolphat Atsawawaranunt; Katarina C. Stuart; Annabel Whibley; Kyle M. Ewart; Lee A. Rollins; Rebecca N. Johnson; Anna W. Santure (Molecular Ecology, 2026)
Researchers must navigate several trade‐offs when deciding which population sequencing method to use. The decision between reduced representation approaches and whole genome sequencing (WGS) impacts marker density, sequencing depth and costs per sample, which will in turn affect the power to accurately characterise certain genomic features, such as regions of the genome exhibiting signals of selection. To investigate the effect of sequencing method on the detection of putatively adaptive regions, we compared selection scan analyses of a set of restriction site‐associated DNA sequencing (RADseq) datasets for the common myna ( Acridotheres tristis ) with a WGS dataset with fewer individuals. Although selection scan statistics were found to be correlated between datasets, no common outliers were found when using outlier thresholds typically applied in such studies. We compared allele frequencies and genotypes across datasets and found that discordances were due to missing markers, different individuals sampled or erroneous genotyping. Most importantly, two regions with strong signals of selection identified through WGS data were missed in the lower density dataset, and population‐specific allelic dropout, which can result from restriction enzyme cut site loss in RADseq, created false signals of selection in these datasets. Our results highlight the advantages of WGS over RADseq when used for selection scan analyses, especially for highly structured populations such as those observed in many invasive or endangered species.

A Beginner's Guide to Structural Variants in Eco‐Evolutionary Population Genomics - Katarina C. Stuart; Rebekah A. Oomen; Anna Tigano; Maren Wellenreuther; Jana Wold; David L. Field; Claire Mérot (Molecular Ecology, 2026)
Whole‐genome sequencing (WGS) has greatly expanded researchers' ability to study structural variants (SVs), that is, the variation in the presence, number, orientation or position of a DNA sequence. This has paved the way to study the eco‐evolutionary dynamics of SVs across the tree of life and within a population genomics framework. In this review, we provide the necessary fundamentals to help researchers generate and analyse population‐level SV data. We discuss the unique properties of different SV groups and how these fundamental differences interact with important biological and evolutionary processes using both empirical results and theory. This includes discussion of unresolved issues around SVs, such as technical difficulties in identification, accounting for diversity and evaluating functional effects. We explicitly integrate into this discussion transposable elements, which are an important component of SVs often identified in population‐level variant data. Finally, we focus on the practical side of SV analysis, offering a framework for SV identification and data analysis. In particular, we examine the heterogeneous nature of SV properties (type, length, sequence identity) that should be considered when studying them in ecology and evolution. This review aims to provide resources and guidelines to help researchers navigate the complexities of a relatively new field of eco‐evolutionary genomics research.

Drought Response Is Not a Species Trait: Tropical Tree Drought Sensitivity Is Shaped by Drought Characteristics, Species Adaptations and Individual Microenvironments - Krishna Anujan; Sean M. McMahon; Sarayudh Bunyavejchewin; Stuart J. Davies; Helene C. Muller‐Landau; Nantachai Pongpattananurak; Kristina J. Anderson‐Teixeira (Ecology Letters, 2026)
Increased frequency and severity of droughts threatens forest health worldwide. Tree species‐specific adaptations—for example, dry‐season deciduousness in tropical seasonal forests—and individual traits—for example, size, crown position—shape drought resistance, but such resistance may be variable across species, microenvironments and drought events. Here, we assess growth responses of 1820 trees across 30 species to three climatically distinct droughts in a seasonally dry tropical forest in Western Thailand. Species and individuals exhibited a wide range of growth responses within each drought, and differences in response intensity and affect among the drought events. Deciduous and evergreen species were more sensitive to wet‐ and dry‐season drought respectively. While individuals with more exposed crowns tended to grow less in all droughts, stem diameter and topographic wetness had variable effects. Heterogeneous drought responses of species and individuals indicate potential biological insurance effects in diverse forests in the face of increased drought.

Both Structural Variant and Single Nucleotide Polymorphism Load Impact Lifetime Fitness in a Threatened Bird Species - Katarina C. Stuart; Hui Zhen Tan; Annabel Whibley; Sarah Bailey; Patricia Brekke; John G. Ewen; Selina Patel; Anna W. Santure (Molecular Ecology, 2025)
The field of conservation genomics is becoming increasingly interested in whether, and how, structural variant (SV) genotype information can be leveraged in the management of threatened species. The functional consequences of SVs are more complex than for single nucleotide polymorphisms (SNPs), as SVs typically impact a larger proportion of the genome due to their size and thus may be more likely to contribute to load. While the impacts of SV‐specific genetic load may be less consequential for large populations, the interplay between weakened selection and stochastic processes means that smaller populations, such as those of the threatened Aotearoa hihi/New Zealand stitchbird ( Notiomystis cincta ), may harbour a high SV load. Hihi were once confined to a single remnant population, but have been reestablished into six sanctuaries and reserves, often via secondary bottlenecks, resulting in low genetic diversity, low adaptive potential, and inbreeding depression. In this study, we use whole genome resequencing of 30 individuals from the Tiritiri Matangi population to identify the nature and distribution of both SNPs and SVs within this small avian population. We find that SNP and SV individual mutation load is only moderately correlated, likely because SVs arise in regions of high recombination and that are less evolutionarily conserved. Finally, we leverage a long‐term monitoring dataset of pedigree and fitness data to assess the impact of SNP and SV mutation loads on individual fitness, and find that SNP and SV realised load had similar negative correlations with lifetime fitness. However, of the masked load metrics, only SVs had a positive significant correlation with lifetime fitness, indicating that masking of deleterious alleles may be more important for SVs than for SNPs. The results of this study indicate that only examining SNPs neglects important aspects of intra‐specific variation and that studying SVs has direct implications for linking genetic diversity and genomic health to inform management decisions.

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

The first report of Hematodinium perezi genotype I infection of Chinese mitten crab (Eriocheir sinensis) from the River Thames, UK - Rose C. Kerr; Hamish J. Small; David Bass; Wafa S. Al Arimi; Stuart Ross; Roland Pevsner; Bryony Williams; Ronny van Aerle; Grant Stentiford; Kelly Bateman (Journal of Invertebrate Pathology, 2025)

Precision in Spinal Cord Injury Research: A Novel Electromagnetic Impactor for a Consistent Porcine Model - Leonard Steger; Abdul Karim Ghaith; Carly Weber-Levine; Kayla Robinson; Christina Krueger; Constantin Smit; Siddharth Krishnan; Kelley M. Kempski Leadingham; Daniel Davidar; Denis Routkevitch; Kelly Jiang; Victor Quiroz; et al. (Annals of Biomedical Engineering, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Ammonia and organic carbon transformation in autogenic continuous flow supercritical water oxidation reactor - Jianna Li; Conrad Austin; Stuart Moore; Anmol Purohit; Shuzhong Wang; Jun Hu; Nizette Consolazio; John C. Kramlich; Igor V. Novosselov (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of the temporal abundance of the epiphytic pest, Melanothamnus thailandicus, affecting farmed Kappaphycus striatus: Visual and molecular detection approaches - Joseph P. Faisan; Rema C. Sibonga; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Jonalyn P. Mateo; Janina Brakel; Juliet Brodie; Georgia M. Ward; David Bass; Stuart Ross; Grant D. Stentiford; Claire Gachon; et al. (Journal of Applied Phycology, 2025)

Population Genetics and Invasion History of the European Starling Across Aotearoa New Zealand - Bryan Thompson; Kamolphat Atsawawaranunt; Melissa C. Nehmens; William S. Pearman; E. Owen Perkins; Pavel Pipek; Lee A. Rollins; Hui Zhen Tan; Annabel Whibley; Anna W. Santure; Katarina C. Stuart (Molecular Ecology, 2025)
The expansion of human settlements over the past few centuries is responsible for an unprecedented number of invasive species introductions globally. An important component of biological invasion management is understanding how introduction history and postintroduction processes have jointly shaped present‐day distributions and patterns of population structure, diversity and adaptation. One example of a successful invader is the European starling ( Sturnus vulgaris ), which was intentionally introduced to numerous countries in the 19th century, including Aotearoa New Zealand, where it has become firmly established. We used reduced representation sequencing to characterise the genetic population structure of the European starling in New Zealand, comparing it to that present in sampling locations in the native range and invasive Australian range. The population structure and genetic diversity patterns we found suggested restricted gene flow from the majority of New Zealand to the northmost sampling location (Auckland). We also profiled genetic bottlenecks and shared outlier genomic regions, which supported historical accounts of translocations between both Australian subpopulations and New Zealand, and provided evidence of which documented translocation events were more likely to have been successful. Using these results as well as historic demographic patterns, we demonstrate how genomic analysis complements even well‐documented invasion histories to better understand invasion processes, with direct implications for understanding contemporary gene flow and informing invasion management.

Development and performance evaluation of an analytical method for the analysis of polychlorinated naphthalenes (PCNs) and polychlorinated biphenyls (PCBs) accumulated in pine needles - Sung-Hee Seo; Adriana C. Torres-Moreno; Stuart Batterman (Chemosphere, 2025)

The influence of primary depositional conditions on Hg behaviour during early thermal maturation - Asri O. Indraswari; Joost Frieling; Erdem Idiz; Tamsin A. Mather; Alexander J. Dickson; Hugh C. Jenkyns; Stuart A. Robinson; Isabel M. Fendley; Oliver Neilson (Chemical Geology, 2025)

Limited mercury (Hg) partitioning into bitumen and efficient gaseous Hg reabsorption during early thermal maturation of organic-rich mudrocks - Asri O. Indraswari; Joost Frieling; Erdem Idiz; Tamsin A. Mather; Hugh C. Jenkyns; Stuart A. Robinson; Alexander J. Dickson (Geochimica et Cosmochimica Acta, 2025)

Body size rather than reflectivity explains thermal constraints on colour variation in an aposematic jewel bug - Kei-Lin M. Ooi; Iliana Medina; Fabian C. Salgado-Roa; Devi Stuart-Fox (Evolutionary Ecology, 2025)
Theory posits that warning signals should converge phenotypically to reinforce predator memory, yet many aposematic species show substantial variation in warning signals within and between populations. This could be explained by alternative selective pressures on phenotype beyond predation such as thermoregulation, but empirical tests are scarce and do not consider the full spectrum of sunlight. To examine whether trade-offs with thermoregulation could explain variation in warning colouration, we examined thermal properties of colour variants of the aposematic cotton harlequin bug ( Tectocoris diophthalmus ). This species shows striking variation in warning signals: it is sexually dichromatic, varies within sexes, and shows clinal variation in colour frequencies, with iridescent blue-green colouration prevalent in cooler climates and non-iridescent red–orange colouration prevalent in warmer climates. We quantified reflectivity between colour variants over the full solar spectrum and investigated the contribution of ultraviolet and visible (UV–visible, 300–700 nm) and near infrared (NIR, 700–1700 nm) light on heating. Differences in reflectivity of iridescent and non-iridescent colour patches were greater in NIR than UV–visible wavelengths but did not result in significant differences in heating. However, we found a tight link between body size and reflectivity, with smaller males having lower reflectivity and heating faster. Due to the strong correlation between body size and colouration, thermal constraints related to body size may help to explain the observed clinal variation in colour frequencies.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

ESG mapping of the Australian mining sector – The state of play on mobilising spatial datasets for decision making - Eléonore Lèbre; Karol Czarnota; Stuart D.C. Walsh; Marcus Haynes; Natasha Ufer; Laura J. Sonter; Rachakonda Sreekar; Pascal Bolz; Nevenka Bulovic; Claire Côte; Nadja C. Kunz; Steven Micklethwaite; et al. (Resources Policy, 2025)

Genome-wide association for precocial maturation in juvenile male Spring Chinook salmon (Oncorhynchus tshawytscha) - Nick F. Hoffman; Stuart C. Willis; Hayley M. Nuetzel; Andrew L. Pierce; James J. Nagler; Shawn R. Narum (Conservation Genetics, 2025)
Fish conservation through hatchery supplementation involves maintaining population structure similar to natural populations. High proportions of precociously mature two-year-old male Chinook salmon (i.e. minijacks) observed in hatchery populations reduces the number of anadromous males in the population. Understanding the genetic architecture of this trait could be used to adjust hatchery practices to reduce precocious maturation. The genetic control of this trait was examined in a hatchery population of Columbia River Spring Chinook salmon over two replicate year classes (brood years BY2018 and BY2019). Genome wide allele frequencies from millions of single nucleotide polymorphisms (SNPs) were compared between immature males and minijacks identified by plasma 11-ketotestosterone levels. Genome scans identified 1,917 SNPs within and between brood years. Within brood years, there were two and four notable peaks of significance in BY2018 and BY2019, respectively. Combining the same phenotypes between brood years resulted in candidate regions on multiple chromosomes associated with precocial maturation as a minijack. The strongest signals from the combined year analysis were on chromosomes 15 (617 SNPs, five genes) and 18 (922 SNPs, nine genes). Individuals representing the extreme ends of the phenotypic distributions had notable signals on chromosomes 17 and 18, which have been previously identified as age-of-maturity candidates in this species. These analyses indicated that genetic control of minijack maturation is influenced by many regions of small effect including markers that may be sex-linked on chromosomes 17 and 18. The regions identified in this study will aid in conservation and broodstock monitoring relating to abundances of minijacks in hatchery origin populations.

Sugarcane (Saccharum spp. hybrids) biotechnology research in South Africa - Sandra J. Snyman; Aimee C. Koch; Robyn M. Jacob; Shailesh V. Joshi; Sharon A. McFarlane; Christell van der Vyver; R. Stuart Rutherford (In Vitro Cellular & Developmental Biology - Plant, 2025)
Commercial sugarcane, Saccharum spp. hybrids, arose from interspecific crossing in the late 1890s and the resultant complex polyploid genome has challenged conventional breeding approaches. The grower- and miller-funded South African Sugarcane Research Institute (SASRI) has a 100-yr history which began by breeding for local agroclimatic regions. Biotechnology for cultivar improvement was introduced in the early 1990s. Collaborations with local research institutes and the International Consortium for Sugarcane Biotechnology (ICSB) have enabled advances such as the genome sequence being published this year, signifying a real opportunity to implement bioinformatic and marker techniques for targeted cultivar enhancement. This review focuses on biotechnology-related interventions that have supported sugarcane research and resulted in SASRI-bred N cultivars being widely grown in many sub-Saharan African sugarcane-growing countries.

Synthesis of zeolites from different kaolin deposits worldwide - Abdulsalami S. Kovo; Stuart M. Holmes; Carlos A. Rios; Abdulrazak J. Otaru; Ambali S. Abdulkareem; Victoria C. Eluwa (Applied Clay Science, 2025)

Isolation and characterisation of two epithelial-like cell lines from the gills of Chrysophrys auratus (Australasian snapper) and Oncorhynchus tshawytscha (Chinook salmon) and their use in aquatic toxicology - Björn Böhmert; Gavril L. W. Chong; Kim Lo; Michael Algie; Damon Colbert; Melissa D. Jordan; Gabriella Stuart; Lyn M. Wise; Lucy E. J. Lee; Niels C. Bols; Georgina C. Dowd (In Vitro Cellular & Developmental Biology - Animal, 2025)
In vitro gill models are becoming increasingly important in aquatic toxicology, yet the fish gill invitrome is underrepresented, encompassing approximately 0.1% of extant species. Here, we describe the establishment and characterisation of two gill-derived, epithelial-like cell lines isolated from fish species of significant importance to New Zealand: Chrysophrys auratus (Australasian snapper) and Oncorhynchus tshawytscha (Chinook salmon). Designated CAgill1PFR ( Chrysophrys auratus, gill 1 , P lant & F ood R esearch) and OTgill1PFR ( Oncorhynchus tshawytscha, gill 1 , P lant & F ood R esearch), these cell lines have each been passaged greater than each 70 times over several years and are considered spontaneously immortalised. Both cell lines required serum for growth and exhibited differential responses to basal media formulations. CAgill1PFR was sensitive to low temperatures (4 °C) but replicated at high temperatures (30 °C), whereas OTgill1PFR was sensitive to high temperatures but remained viable at low temperatures, mirroring the natural environment of their host species. Immunostaining revealed expression of epithelial cell markers cytokeratin and E-cadherin, alongside positivity for the mesenchymal cell marker, vimentin. CAgill1PFR was more sensitive to the environmental toxin 3,4 dichloroaniline than OTgill1PFR through measurements of metabolic activity, membrane integrity, and lysosomal function. Furthermore, CAgill1PFR produced less CYP1A activity, indicative of ongoing biotransformation processes, in response to beta-naphthoflavone than OTgill1PFR. These cell lines expand the toolbox of resources and emphasise the need for species-specific aquatic toxicology research.

Comparison of naturally altered archaeological glasses from a marine environment with accelerated laboratory tests; implications for modelling long-term corrosion - Clare L. Thorpe; Nick Aldred; Stuart Creasey-Gray; Martin C. Stennett; Eperke A. Rencz; Susan Nehzati; Latham T. Haigh; Garry Manifold; Nishta Vallo; Christoph Lenting; Claire L. Corkhill; Russell J. Hand (Applied Geochemistry, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The End of an Era? Trends in Abundance and Reproduction of Australian Southern Right Whales ( Eubalaena australis ) Suggest Failure to Re‐Establish Pre‐Whaling Population Size - Anne Grundlehner; Joshua N. Smith; John L. Bannister; Virginia Andrews‐Goff; Madeleine Brasier; Micheal C. Double; Stuart P. Corney (Global Change Biology, 2025)
The large‐scale exploitation of whale populations in the whaling era led to the near extirpation of large whales all over the world. This must have had major repercussions for marine ecosystems globally. Consequent changes to those ecosystems and physical environments create uncertainty around whether present‐day conditions are adequate to support full recovery of pre‐whaling population sizes. Combined with potential effects of anthropogenic stressors, the future viability of exploited whale populations is questioned. This migrating species was left near extinction from whaling and has shown slow, yet steady, recovery in recent decades. Here, we collate abundance data from aerial surveys performed along the Australian coast between 1976 and 2024, covering 2250 km of coastal habitat, to study the recovery trajectory of Australian southern right whales ( Eubalaena australis ). We describe temporal trends in abundance, reproduction and growth of the western sub‐population. Our study reveals that despite previously displaying exponential growth, and a present population size still residing far below pre‐whaling levels, annual births have started declining since 2016 and annual abundances of unaccompanied individuals have dropped by 66%. Our results suggest the end of an era of this population's recovery, highlighting that an initial period of steady recovery does not guarantee successful re‐establishment of previous abundance levels.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Galactic cosmic ray environment predictions for the NASA BioSentinel Mission, part 2:Post-mission validation - Shirin Rahmanian; Tony C. Slaba; Stuart George; Leslie A. Braby; Sharmila Bhattacharya; Tore Straume; Sergio R. Santa Maria (Life Sciences in Space Research, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Parallel Signatures of Diet Adaptation in the Invasive Common Myna Genome - Kamolphat Atsawawaranunt; Katarina C. Stuart; Annabel Whibley; Kyle M. Ewart; Richard E. Major; Rebecca N. Johnson; Anna W. Santure (Molecular Ecology, 2025)
Invasive species offer uniquely replicated model systems to study rapid adaptation. The common myna ( Acridotheres tristis ) has been introduced to over a dozen countries and is classified as one of the most invasive birds in the world. Their multiple invasions provide an opportunity to identify repeated adaptation, as invasive populations originated from multiple source populations. We compared whole‐genome resequencing data from 80 individuals from four native and seven invasive populations, representing two independent introduction pathways. Results from two different selection scan methods were combined and identified a strongly selected region on chromosome 8 that spans two copies of AMY2A, part of the alpha‐amylase gene family, a putative ncRNA and an insertion–deletion structural variant (SV) that contains an ERVK transposable element (TE). Outlier SNPs and the SV are polymorphic in native populations, but fixed or close‐to‐fixed in the two invasive pathways, with the fixation of the same alleles in two independent lineages providing evidence for parallel selection on standing variation. Intriguingly, the second copy of AMY2A has a non‐conservative missense mutation at a phylogenetically conserved site. This mutation, alongside variation in the SV, TE and ncRNA, provide possible routes for changes to protein function or expression. AMY2A has been associated with human commensalism in house sparrows, and genes in this family have been linked to adaptation to high‐starch diets in humans and dogs. This study illustrates the value of replicated analyses within and across species to understand rapid adaptation at the molecular level.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Widespread upper-ocean deoxygenation in the Alpine-Mediterranean Tethys during the Toarcian Oceanic Anoxic Event - Wenhan Chen; David B. Kemp; Hugh C. Jenkyns; Stuart A. Robinson; Shouyi Jiang; Chengrong Pan; Chao Li (Global and Planetary Change, 2024)

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Smartphone-based hyperspectral imaging for ice sheet and proglacial applications in South-West Greenland - M.B. Stuart; M. Davies; C. Fisk; E. Allen; A.J. Sole; R. Ing; M.J. Hobbs; J.R. Willmott (Science of The Total Environment, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Exome variant prioritization in a large cohort of hearing-impaired individuals indicates IKZF2 to be associated with non-syndromic hearing loss and guides future research of unsolved cases - Hedwig M. Velde; Maryam Vaseghi-Shanjani; Jeroen J. Smits; Gayatri Ramakrishnan; Jaap Oostrik; Mieke Wesdorp; Galuh Astuti; Helger G. Yntema; Lies Hoefsloot; Cris P. Lanting; Martijn A. Huynen; Anna Lehman; et al. (Human Genetics, 2024)
Although more than 140 genes have been associated with non-syndromic hereditary hearing loss (HL), at least half of the cases remain unexplained in medical genetic testing. One reason is that pathogenic variants are located in ‘novel’ deafness genes. A variant prioritization approach was used to identify novel (candidate) genes for HL. Exome-wide sequencing data were assessed for subjects with presumed hereditary HL that remained unexplained in medical genetic testing by gene-panel analysis. Cases in group AD had presumed autosomal dominantly inherited HL (n = 124), and in group AR, presumed autosomal recessive HL (n = 337). Variants in known and candidate deafness genes were prioritized based on allele frequencies and predicted effects. Selected variants were tested for their co-segregation with HL. Two cases were solved by variants in recently identified deafness genes ( ABHD12 , TRRAP ). Variant prioritization also revealed potentially causative variants in candidate genes associated with recessive and X-linked HL. Importantly, missense variants in IKZF2 were found to co-segregate with dominantly inherited non-syndromic HL in three families. These variants specifically affected Zn 2+ -coordinating cysteine or histidine residues of the zinc finger motifs 2 and 3 of the encoded protein Helios. This finding indicates a complex genotype–phenotype correlation for IKZF2 defects, as this gene was previously associated with non-syndromic dysfunction of the immune system and ICHAD syndrome, including HL. The designed strategy for variant prioritization revealed that IKZF2 variants can underlie non-syndromic HL. The large number of candidate genes for HL and variants therein stress the importance of inclusion of family members for variant prioritization.

Combining the uncombinable: corporate memories, ethnobiological observations, oceanographic and ecological data to enhance climatic resilience in small-scale fisheries - Isabel Garibay-Toussaint; Carolina Olguín-Jacobson; C. Brock Woodson; Nur Arafeh-Dalmau; Jorge Torre; Stuart Fulton; Fiorenza Micheli; Ryan O’Connor; Magdalena Précoma-de la Mora; Arturo Hernández-Velasco; Nemer E. Narchi (Frontiers in Marine Science, 2024)
The global food production system is increasingly strained by abrupt and unpredictable weather events, which hinder communities' ability to adapt to climate variations. Despite advances in meteorological predictions, many communities lack the academic knowledge or infrastructure to interpret these complex models. This gap highlights the need for solutions that make climate forecasts more accessible and actionable, especially for communities reliant on natural resources. This study explores the potential of enhancing seasonal climate forecasts by integrating local ecological knowledge (LEK) with scientific data. Specifically, we combined ethnobiological information gathered between 2022 and 2024 with existing oceanographic and ecological data to create an ethnobiological calendar for four fishing cooperatives. An ethnographic approach was used to understand the population's ethnobiological knowledge and their perceptions of marine heatwaves and climate change impacts. Coastal monitoring data was collected using moorings that recorded temperature over a 14-year period (2010–2024). To characterize giant kelp dynamics, we used an existing dataset of multispectral Landsat images, which estimates the surface canopy biomass of giant kelp forests. Ecological monitoring was conducted annually every summer from 2006 to 2023 to record the in situ abundance of ecologically and economically important invertebrate and fish species. Combining oceanographic, ecological, and ethnographic data, allowed for alligning fishers' observations with recorded marine heatwave events and ecological shifts. Our findings revealed that these observations closely matched documented marine heatwave data and corresponding ecological changes. The integration of LEK with scientific oceanographic data can significantly improved our understanding of dynamic climate regimes, offering contextually relevant information that enhances the reliability and utility of seasonal climate forecasts. By incorporating yearly data into an ethnobiological calendar, we promote more inclusive, community-based approaches to environmental management, advocating for the integration of LEK in climate adaptation efforts, emphasizing its crucial role in strengthening resilience strategies against climatic shocks.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Observations of phytoplankton productivity and growth rates in the Malin shelf break environment - Stuart C. Painter (Continental Shelf Research, 2024)

Temporal variation in the incidence of seaweed health problems affecting farmed Kappaphycus striatus in relation to environmental conditions in shallow waters - Joseph P. Faisan; Rema C. Sibonga; Jonalyn P. Mateo; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Vicente T. Balinas; Janina Brakel; David Bass; Stuart Ross; Grant D. Stentiford; Juliet Brodie; Georgia M. Ward; et al. (Journal of Applied Phycology, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

PyShoreVolume 1.0.0: A Python based Shoreline Change and beach Volumetric Change Analysis tool - Owen C. James; Daniel N. Schillereff; Stuart W.D. Grieve; Andreas C.W. Baas (Computers & Geosciences, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Multivalent cations modulating microstructure and interactions of potato protein and fungal hyphae in a functional meat analogue - Mary C. Okeudo-Cogan; Shuyue Yang; Brent S. Murray; Rammile Ettelaie; Simon D. Connell; Stewart Radford; Stuart Micklethwaite; Yoselin Benitez-Alfonso; Richa Yeshvekar; Anwesha Sarkar (Food Hydrocolloids, 2024)

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Interrelationships and biogeography of the New World pufferfish genus Sphoeroides (Tetraodontiformes: Tetraodontidae) inferred using ultra-conserved DNA elements - Elizabeth P. Hunt; Stuart C. Willis; Kevin W. Conway; David S. Portnoy (Molecular Phylogenetics and Evolution, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Beech bark disease does not reduce the long-term wood production of two forests contrasting in age, productivity, and structure - Ellen Stuart-Haëntjens; Jeff W. Atkins; Alexander T. Fotis; Robert T. Fahey; Brady S. Hardiman; Brandon C. Alveshere; Christoph Vogel; Christopher M. Gough (Forest Ecology and Management, 2023)

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Which side are you on? Spider web positioning affects prey capture more than body colour - Fabian C. Salgado-Roa; Devi Stuart-Fox; Edwin Castañeda; Maira S. Tique Obando; Iliana Medina (Evolutionary Ecology, 2023)
Colour has been hypothesized to play a crucial role in prey capture for sit-and-wait predators that rely on visual cues to deceive their prey. Prey capture success has been directly linked to colouration in spiders; however, evidence so far focuses mostly on dorsal colouration, excluding ventral patterns that are visible to prey and may be relevant for prey attraction. Here, we explored whether the dorsal and ventral colouration of a colour polymorphic spider is associated with light environment and prey capture success. We quantified the number of prey captured across three dorsal (black, white, and yellow) and two ventral (black and a mosaic yellow/orange pattern) morphs of Gasteracantha cancriformis , considering light intensity on dorsal and ventral sides. We found that spiders capture more prey in low light environments, and that individuals often expose their dorsal colouration towards low light levels. We did not find significant differences in prey capture rate between morphs dorsally or ventrally. These results indicate that how and where spiders position their web can be more important for prey capture than colouration. Alternative hypotheses such as aposematism, camouflage and thermoregulation deserve more attention in future studies that aim to understand the role of colouration in spiders and the factors causing spider colour polymorphisms.

Correction to: Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)

Avian diversity and function across the world's most populous cities - James Richardson; Alexander C. Lees; Eliot T. Miller; Stuart J. Marsden (Ecology Letters, 2023)
Understanding the composition of urban wildlife communities is crucial to promote biodiversity, ecosystem function and links between nature and people. Using crowdsourced data from over five million eBird checklists, we examined the influence of urban characteristics on avian richness and function at 8443 sites within and across 137 global cities. Under half of the species from regional pools were recorded in cities, and we found a significant phylogenetic signal for urban tolerance. Site‐level avian richness was positively influenced by the extent of open forest, cultivation and wetlands and avian functional diversity by wetlands. Functional diversity co‐declined with richness, but groups including granivores and aquatic birds occurred even at species‐poor sites. Cities in arid areas held a higher percentage of regional species richness. Our results indicate commonalities in the influence of habitat on richness and function, as well as lower niche availability, and phylogenetic diversity across the world's cities.

Understanding the microstructure of a functional meat analogue: Demystifying interactions between fungal hyphae and egg white protein - Mary C. Okeudo-Cogan; Brent S. Murray; Rammile Ettelaie; Simon D. Connell; Stewart J. Radford; Stuart Micklethwaite; Anwesha Sarkar (Food Hydrocolloids, 2023)

Reconstructing mechanisms of extinctions to guide mammal conservation biogeography - Sean Tomlinson; Mark V. Lomolino; John C. Z. Woinarski; Brett P. Murphy; Elizabeth Reed; Chris N. Johnson; Sarah Legge; Kristofer M. Helgen; Stuart C. Brown; Damien A. Fordham (Journal of Biogeography, 2023)
An emerging research program on population and geographic range dynamics of Australia's mammals illustrates an approach to better understand and respond to geographic range collapses of threatened wildlife in general. In 1788, Europeans colonized an Australia with a diverse and largely endemic mammal fauna, where many species that are now extinct or threatened were common and widespread. Subsequent population declines, range collapses and extinctions were caused by introduced predators and herbivores, altered land use, modified fire regimes and the synergies between these threats. Declines in population and range size continue for many Australian mammals despite legislative protection and conservation interventions. Here, we propose an approach that integrates museum data and other historical records into process‐explicit macroecological models to better resolve mammal distributions and abundances as they were at European arrival. We then illustrate how this integrative approach can identify the likely synergistic mechanisms causing mammal population declines across these and other landscapes. This emerging research approach, undertaken with fine temporal and spatial resolution, but at large geographic scales, will provide valuable insights into the different pathways to, and drivers of, extinction. Such insights may, in turn, underpin conservation strategies based on a process‐explicit understanding of population decline and range collapse under alternative scenarios of impending climate and environmental change. Given that similar information is available for other regional biotas, the approach we describe here can be adapted to conserve threatened wildlife in other regions across the globe.

Successful use of sexed stallion semen for in vitro embryo production; a preliminary study - Pouya Dini; Alejandro de la Fuente; Juan C Samper; Cristina Cabrera; GR Holyoak; Sheila Megehee; Stuart A Meyers (Journal of Equine Veterinary Science, 2023)

Phenotypic Variation in Phytochemical Defense of Trembling Aspen in Western North America: Genetics, Development, and Geography - Richard L. Lindroth; Stuart C. Wooley; Jack R. Donaldson; Kennedy F. Rubert-Nason; Clay J. Morrow; Karen E. Mock (Journal of Chemical Ecology, 2023)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Socially transferred materials: why and how to study them - Sanja Maria Hakala; Haruna Fujioka; Katharina Gapp; Ornela De Gasperin; Eléonore Genzoni; Rebecca M. Kilner; Joris M. Koene; Barbara König; Timothy A. Linksvayer; Marie-Pierre Meurville; Matteo A. Negroni; Hugo Palejowski; et al. (Trends in Ecology & Evolution, 2023)

Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)
Few invasive birds are as globally successful as the Common or European Starling ( Sturnus vulgaris ). Native to the Palearctic, the starling has been intentionally introduced to North and South America, South Africa, Australia, and the Pacific Islands, enabling us to explore species traits that may contribute to its invasion success. Coupling the rich studies of life history and more recent explorations of genomic variation among invasions, we illustrate how eco-evolutionary dynamics shape the invasion success of this long-studied and widely distributed species. Especially informative is the comparison between Australian and North American invasions, because these populations colonized novel ranges concurrently and exhibit shared signals of selection despite distinct population histories. In this review, we describe population dynamics across the native and invasive ranges, identify putatively selected traits that may influence the starling’s spread, and suggest possible determinants of starling success world-wide. We also identify future opportunities to utilize this species as a model for avian invasion research, which will inform our understanding of species’ rapid evolution in response to environmental change.

Controlling common carp (Cyprinus carpio): barriers, biological traits, and selective fragmentation - M. L. Piczak; P. A. Bzonek; T. C. Pratt; P. W. Sorensen; I. G. Stuart; T. Theÿsmeÿer; N. E. Mandrak; J. D. Midwood; S. J. Cooke (Biological Invasions, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

Inter-colony and inter-annual variation in discard use by albatross chicks revealed using isotopes and regurgitates - Amanda Kuepfer; Paulo Catry; Stuart Bearhop; Richard B. Sherley; Olivia Bell; Jason Newton; Paul Brickle; Alexander Arkhipkin; Stephen C. Votier (Marine Biology, 2023)
Effective marine ecosystem monitoring is critical for sustainable management. Monitoring seabird diets can convey important information on ecosystem health and seabird–fishery interactions. The diet of breeding black-browed albatross ( Thalassarche melanophris ) has previously been assessed using stomach content analysis (SCA) or stable isotope analysis (SIA), but not both methods together. Combining dietary sampling approaches reduces biases associated with using single methods. This study combines SCA and SIA to study the diet of black-browed albatross chicks, with a specific focus on fishery discard consumption, at two Falkland Islands colonies (New Island 51°43′S, 61°18′W and Steeple Jason Island 51°01′S, 61°13′W) during two consecutive breeding seasons (2019 and 2020). SCA provided high taxonomic resolution of short-term diet and priors for stable isotope mixing models, with multiple measures of dietary items (e.g. numeric frequency N%, frequency of occurrence FO%). By contrast, SIA of down feathers provided a single and more integrated dietary signal from throughout chick development. Although the two methods disagreed on the dominant prey group (SCA—crustacean; SIA—pelagic fish), the complementary information suggested a chick diet dominated by natural prey (SCA: 74%–93% [FO], 44%–98% [N]; SIA: minimum 87%–95% contribution). Nonetheless, SCA revealed that a high proportion of breeding adults do take discards. We detected consistent colony-specific diets in relation to prey species, but not in relation to higher discard use. Overall, discard consumption was highest in 2020, the year characterised by the poorest foraging conditions. Our results have implications for fisheries management and future dietary studies assessing discard use.

Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals - Ayesha I. T. Tulloch; Micha V. Jackson; Elisa Bayraktarov; Alexander R. Carey; Diego F. Correa‐Gomez; Michael Driessen; Ian C. Gynther; Mel Hardie; Katherine Moseby; Liana Joseph; Harriet Preece; Andrés Felipe Suarez‐Castro; et al. (Conservation Biology, 2023)
Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small ( 5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals.

Perfluoroalkyl substances exposure in firefighters: Sources and implications - Paul E. Rosenfeld; Kenneth R. Spaeth; Linda L. Remy; Vera Byers; Stuart A. Muerth; Ryan C. Hallman; Jasmine Summers-Evans; Sofia Barker (Environmental Research, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Landscape -scale predictors of persistence of an urban stock dove Columba oenas population - James Richardson; Alexander C. Lees; Stuart Marsden (Urban Ecosystems, 2023)
While a few species may thrive in urban areas, urban expansion is a major driver of biodiversity loss. Columbids such as feral Rock Doves ( Columba livia domestica ) and Common Woodpigeon ( Columba palumbus ) have adapted extremely well to the urban environment in Europe and beyond, but the Stock Dove ( Columba oenas ), a bird of farmland and woodland edge in the UK and of national conservation concern, is encountered infrequently in urban areas. Here we explore the multi-scale landscape associations of the little-studied Stock Dove within the urban matrix of Greater Manchester, UK, in order to identify its habitat requirements. We built a pilot model from historical citizen science records to identify potentially occupied sites within the city, and then surveyed these sites for Stock Dove during Spring 2019. We combined the survey results with citizen science records from the same period and described the habitat and landscape characteristics of sites occupied by Stock Dove using four variables at different scales plus twelve unscaled variables. We used a three-stage random forest approach to identify a subset of these variables for interpretation and a subset for prediction for the presence of Stock Dove within these sites. Key variables for predicting Stock Dove presence were their relative abundance in the landscape immediately beyond the core urban area, the greenness (NDVI) of the environment around sites, and the canopy cover of individual trees over 20 m high within sites. Stock Doves tended to be associated with habitats with more surface water during the non-breeding season than the breeding season. Our results highlight the importance of large trees within urban greenspace for this cavity-nesting species, softer boundaries around urban sites for Stock Doves and stock dove presence in nearby areas. While Stock Dove share many traits with species that are successful in the urban environment, they remain relatively poor urban adapters.

Coastal freshening drives acidification state in Greenland fjords - Henry C. Henson; Johnna M. Holding; Lorenz Meire; Søren Rysgaard; Colin A. Stedmon; Alice Stuart-Lee; Jørgen Bendtsen; Mikael Sejr (Science of The Total Environment, 2023)

Can Aphid Herbivory Induce Intergenerational Effects of Endophyte-conferred Resistance in Grasses? - Ludmila M. Bubica Bustos; Andrea C. Ueno; Fernando Biganzoli; Stuart D. Card; Wade J. Mace; María A. Martínez-Ghersa; Pedro E. Gundel (Journal of Chemical Ecology, 2022)

Range and extinction dynamics of the steppe bison in Siberia: A pattern‐oriented modelling approach - July A. Pilowsky; Sean Haythorne; Stuart C. Brown; Mario Krapp; Edward Armstrong; Barry W. Brook; Carsten Rahbek; Damien A. Fordham (Global Ecology and Biogeography, 2022)
Aim To determine the ecological processes and drivers of range collapse, population decline and eventual extinction of the steppe bison in Eurasia. Location Siberia. Time period Pleistocene and Holocene. Major taxa studied Steppe bison ( Bison priscus ). Methods We configured 110,000 spatially explicit population models (SEPMs) of climate–human–steppe bison interactions in Siberia, which we ran at generational time steps from 50,000 years before present. We used pattern‐oriented modelling (POM) and fossil‐based inferences of distribution and demographic change of steppe bison to identify which SEPMs adequately simulated important interactions between ecological processes and biological threats. These “best models” were then used to disentangle the mechanisms that were integral in the population decline and later extinction of the steppe bison in its last stronghold in Eurasia. Results Our continuous reconstructions of the range and extinction dynamics of steppe bison were able to reconcile inferences of spatio‐temporal occurrence and the timing and location of extinction in Siberia based on hundreds of radiocarbon‐dated steppe bison fossils. We showed that simulating the ecological pathway to extinction for steppe bison in Siberia in the early Holocene required very specific ecological niche constraints, demographic processes and a constrained synergy of climate and human hunting dynamics during the Pleistocene–Holocene transition. Main conclusions Ecological processes and drivers that caused ancient population declines of species can be reconstructed at high spatio‐temporal resolutions using SEPMs and POM. Using this approach, we found that climatic change and hunting by humans are likely to have interacted with key ecological processes to cause the extinction of the steppe bison in its last refuge in Eurasia.

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Spatiotemporal influences of climate and humans on muskox range dynamics over multiple millennia - Elisabetta Canteri; Stuart C. Brown; Niels Martin Schmidt; Rasmus Heller; David Nogués‐Bravo; Damien A. Fordham (Global Change Biology, 2022)
Processes leading to range contractions and population declines of Arctic megafauna during the late Pleistocene and early Holocene are uncertain, with intense debate on the roles of human hunting, climatic change, and their synergy. Obstacles to a resolution have included an overreliance on correlative rather than process‐explicit approaches for inferring drivers of distributional and demographic change. Here, we disentangle the ecological mechanisms and threats that were integral in the decline and extinction of the muskox ( Ovibos moschatus ) in Eurasia and in its expansion in North America using process‐explicit macroecological models. The approach integrates modern and fossil occurrence records, ancient DNA, spatiotemporal reconstructions of past climatic change, species‐specific population ecology, and the growth and spread of anatomically modern humans. We show that accurately reconstructing inferences of past demographic changes for muskox over the last 21,000 years require high dispersal abilities, large maximum densities, and a small Allee effect. Analyses of validated process‐explicit projections indicate that climatic change was the primary driver of muskox distribution shifts and demographic changes across its previously extensive (circumpolar) range, with populations responding negatively to rapid warming events. Regional analyses show that the range collapse and extinction of the muskox in Europe (~13,000 years ago) was likely caused by humans operating in synergy with climatic warming. In Canada and Greenland, climatic change and human activities probably combined to drive recent population sizes. The impact of past climatic change on the range and extinction dynamics of muskox during the Pleistocene–Holocene transition signals a vulnerability of this species to future increased warming. By better establishing the ecological processes that shaped the distribution of the muskox through space and time, we show that process‐explicit macroecological models have important applications for the future conservation and management of this iconic species in a warming Arctic.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Faster ocean warming threatens richest areas of marine biodiversity - Stuart C. Brown; Camille Mellin; Jorge García Molinos; Eline D. Lorenzen; Damien A. Fordham (Global Change Biology, 2022)
The vulnerability of marine biodiversity to accelerated rates of climatic change is poorly understood. By developing a new method for identifying extreme oceanic warming events during Earth's most recent deglaciation, and comparing these to 21st century projections, we show that future rates of ocean warming will disproportionately affect the most speciose marine communities, potentially threatening biodiversity in more than 70% of current‐day global hotspots of marine species richness. The persistence of these richest areas of marine biodiversity will require many species to move well beyond the biogeographic realm where they are endemic, at rates of redistribution not previously seen. Our approach for quantifying exposure of biodiversity to past and future rates of oceanic warming provides new context and scalable information for deriving and strengthening conservation actions to safeguard marine biodiversity under climate change.

Fluid-Structure Interaction Analyses for Hydro-Elastic Tailoring of a Windsurfer Fin - Miguel Cardoso de Brito; Leigh Stuart Sutherland; José Manuel C. Pereira; Mário Rui Arruda (Journal of Marine Science and Engineering, 2022)
A fully iterative ‘two-way’ fluid-structure interaction (FSI) tool of a commercially available composite windsurfer fin was developed, which was then used to investigate the normally hidden fin behaviour for a range of typical sailing conditions. The ‘two-way’ FSI analysis gave significantly better insights into the fin behaviour than the simpler ‘one-way’ non-iterative analysis. The tool also indicated that hydro-elastic tailoring, via simple reinforcement ply rotations, can produce large changes in tip twist. This gives an opportunity for both improved passive control and higher speeds, without deviating from a hydrodynamically optimal plan form. Inexpensive cantilever tests appear to be sufficient to make qualitative comparisons between the sailing responses of fins with different layups.

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Development of Inspired Therapeutics Pediatric VAD: Computational Analysis and Characterization of VAD V3 - Landon H. Tompkins; Barry N. Gellman; Steven R. Prina; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Gill transcriptome of the yellow peacock bass (Cichla ocellaris monoculus) exposed to contrasting physicochemical conditions - Stuart C. Willis; David E. Saenz; Gang Wang; Christopher M. Hollenbeck; David S. Portnoy; James J. Cai; Kirk O. Winemiller (Conservation Genetics Resources, 2022)

Morphological and Functional Divergence of the Lower Jaw Between Native and Invasive Red Foxes - Colline Brassard; Jesse L. Forbes-Harper; Heather M. Crawford; John-Michael Stuart; Natalie M. Warburton; Michael C. Calver; Peter Adams; Elodie Monchâtre-Leroy; Jacques Barrat; Sandrine Lesellier; Claude Guintard; Hélène Garès; et al. (Journal of Mammalian Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic recruitment patterns are patchy and spatiotemporally unpredictable in a deep-water snapper (Lutjanus vivanus) sampled in fished and protected areas of western Puerto Rico - Stuart C. Willis; Christopher M. Hollenbeck; Jonathan B. Puritz; David S. Portnoy (Conservation Genetics, 2022)

Estimating population size and survival of adult northern pike ( Esox lucius ) in Lower Green Bay - Claire E. Stuart; Jason C. Doll; Patrick S. Forsythe; Zachary S. Feiner (Fisheries Management and Ecology, 2022)
Complex life history behaviours like spawning migrations can complicate population assessments. However, predictable aggregation of populations at certain times of year (e.g. at spawning grounds) presents an effective way to sample species that are otherwise spatially widespread. From 2014 to 2019, a mark‐recapture study on Green Bay northern pike ( Esox lucius ) entering a spawning wetland was used to estimate apparent survival and population size using Bayesian inference and the Cormack–Jolly–Seber model. Population estimates and apparent survival varied from 446 to 1949 and 0.22 (males in 2017) to 0.63 (males in 2015), respectively, among years. Apparent survival also increased with maximum mean daily water temperature. Estimated capture probability was consistently low across years (

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Development of Inspired Therapeutics Pediatric VAD: Benchtop Evaluation of Impeller Performance and Torques for MagLev Motor Design - Landon H. Tompkins; Steven R. Prina; Barry N. Gellman; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

Historical museum samples enable the examination of divergent and parallel evolution during invasion - Katarina C. Stuart; William B. Sherwin; Jeremy J. Austin; Melissa Bateson; Marcel Eens; Matthew C. Brandley; Lee A. Rollins (Molecular Ecology, 2022)
During the Anthropocene, Earth has experienced unprecedented habitat loss, native species decline and global climate change. Concurrently, greater globalization is facilitating species movement, increasing the likelihood of alien species establishment and propagation. There is a great need to understand what influences a species’ ability to persist or perish within a new or changing environment. Examining genes that may be associated with a species’ invasion success or persistence informs invasive species management, assists with native species preservation and sheds light on important evolutionary mechanisms that occur in novel environments. This approach can be aided by coupling spatial and temporal investigations of evolutionary processes. Here we use the common starling, Sturnus vulgaris , to identify parallel and divergent evolutionary change between contemporary native and invasive range samples and their common ancestral population. To do this, we use reduced‐representation sequencing of native samples collected recently in northwestern Europe and invasive samples from Australia, together with museum specimens sampled in the UK during the mid‐19th century. We found evidence of parallel selection on both continents, possibly resulting from common global selective forces such as exposure to pollutants. We also identified divergent selection in these populations, which might be related to adaptive changes in response to the novel environment encountered in the introduced Australian range. Interestingly, signatures of selection are equally as common within both invasive and native range contemporary samples. Our results demonstrate the value of including historical samples in genetic studies of invasion and highlight the ongoing and occasionally parallel role of adaptation in both native and invasive ranges.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Development of Reduced Order Hydro-mechanical Models of Fractured Media - Anil Kumar; Roger Hu; Stuart D. C. Walsh (Rock Mechanics and Rock Engineering, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Fecal steroids as a potential tool for conservation paleobiology in East Africa - Andrew C. Kemp; Christopher H. Vane; Alexander W. Kim; Christopher L. Dutton; Amanda L. Subalusky; Stuart K. Kemp; Andrew C. Parnell (Biodiversity and Conservation, 2022)

Cover Image - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; Julia Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)

Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; July A. Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)
Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Interrelationships Between Coating Uniformity and Efficiency in Pan Coating Processes - Michael Choi; Stuart C. Porter; Axel Meisen (AAPS PharmSciTech, 2021)

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Characterization of clinical Ralstonia strains and their taxonomic position - Ad C. Fluit; Jumamurat R. Bayjanov; María Díez Aguilar; Rafael Cantón; Michael M. Tunney; J. Stuart Elborn; Mireille van Westreenen; Miquel B. Ekkelenkamp (Antonie van Leeuwenhoek, 2021)
To improve understanding of the role of Ralstonia in cystic fibrosis (CF), whole genomes of 18 strains from clinical samples were sequenced using Illumina technology. Sequences were analysed by core genome Multi-Locus Sequence Typing, Average Nucleotide Identity based on BLAST (ANIb), RAST annotation, and by ResFinder. Phylogenetic analysis was performed for the 16S rRNA gene, and the OXA-22 and OXA-60 ß-lactamase families. The minimal inhibitory concentrations (MICs) were determined using broth microdilution. ANIb data for the 18 isolates and 54 strains from GenBank, supported by phylogenetic analysis, showed that 8 groups of clusters (A-H), as well as subgroups that should be considered as species or subspecies. Groups A-C contain strains previously identified as Ralstonia solanacearum and Ralstonia pseudosolanacearum . We propose that group A is a novel species. Group B and C are Ralstonia syzygii , Ralstonia solanacearum , respectively. Group D is composed of Ralstonia mannitolilytica and Group E of Ralstonia pickettii . Group F and G should be considered novel species. Group H strains belong to R. insidiosa . OXA-22 and OXA-60 family ß-lactamases were encoded by all strains. Co-trimoxazole generally showed high activity with low MICs (≤1 mg/l) as did ciprofloxacin (≤0.12 mg/l). MICs against the other antibiotics were more variable, but generally high. RAST annotation revealed limited differences between the strains, and virulence factors were not identified. The taxonomy of the genus Ralstonia is in need of revision, but sequencing additional isolates is needed. Antibiotic resistance levels are high. Annotation did not identify potential virulence factors.

The relationship of C and N stable isotopes to high-latitude moss-associated N2 fixation - Julia E. M. Stuart; Hannah Holland-Moritz; Mélanie Jean; Samantha N. Miller; José Miguel Ponciano; Stuart F. McDaniel; Michelle C. Mack (Oecologia, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Preliminary survey of pests and diseases of eucheumatoid seaweed farms in the Philippines - Joseph P. Faisan; Ma. Rovilla J. Luhan; Rema C. Sibonga; Jonalyn P. Mateo; Victor Marco Emmanuel N. Ferriols; Janina Brakel; Georgia M. Ward; Stuart Ross; David Bass; Grant D. Stentiford; Juliet Brodie; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)

Minor Contribution by Biomineralizing Phytoplankton to Surface Ocean Biomineral Pools in the Late Stratified Period - Stuart C. Painter (Oceans, 2021)
Vertical distributions of biogenic silica (bSi), particulate inorganic carbon (PIC) and key biomineral-forming phytoplankton indicate vertical zoning, or partitioning, during the late summer stratified period in the northeast Atlantic. Coccolithophores were generally more numerous in the surface mixed layer, whilst PIC concentrations were more homogenous with depth throughout the euphotic zone. Diatoms were notably more abundant and more diverse in the lower euphotic zone beneath the mixed layer in association with subsurface maxima in chlorophyll-a, bSi and oxygen concentrations. The four dominant coccolithophore species (Emiliania huxleyi, Gephyrocapsa muellerae, Syracosphera spp., and Rhabdosphaera clavigera) represented 78 ± 20% (range 31–100%) of the observed community across all sampled depths yet simultaneously contributed an average of only 13% to measured PIC pools. The diatom community, which was dominated by Pseudo-nitzschia spp. and by a species tentatively identified as Nanoneis longta, represented only ~1% of the bSi pool on average, with contributions increasing within the chlorophyll maximum. Despite a slow gradual deepening of the surface mixed layer in the period prior to observation, and adequate nutrient availability beneath the mixed layer, biomineral pools at this time consisted largely of detrital rather than cellular material.

Long-term serological follow-up after primary Coxiella burnetii infection in patients with vascular risk factors for chronic Q fever - Sheila B. Buijs; Sanne K. Stuart; Jan Jelrik Oosterheert; Steffi Karhof; Andy I. M. Hoepelman; Nicole H. M. Renders; André S. van Petersen; Chantal P. Bleeker-Rovers; Peter C. Wever; Olivier H. J. Koning (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
We evaluated the long-term serological follow-up of patients with vascular risk factors for chronic Q fever that were previously C oxiella burnetii seropositive. C. burnetii phase I IgG titers were reevaluated in patients that gave informed consent or retrospectively collected in patients already deceased or lost to follow-up. Of 107 patients, 25 (23.4%) became seronegative, 77 (72.0%) retained a profile of past resolved Q fever infection, and five (4.7%) developed chronic Q fever. We urge clinicians to stay vigilant for chronic Q fever beyond two years after primary infection and perform serological testing based on clinical presentation.

Characterization of basal forebrain glutamate neurons suggests a role in control of arousal and avoidance behavior - James T. McKenna; Chun Yang; Thomas Bellio; Marissa B. Anderson-Chernishof; Mackenzie C. Gamble; Abigail Hulverson; John G. McCoy; Stuart Winston; Erik Hodges; Fumi Katsuki; James M. McNally; Radhika Basheer; et al. (Brain Structure and Function, 2021)

A resource-poor developmental diet reduces adult aggression in male Drosophila melanogaster - Danielle Edmunds; Stuart Wigby; Jennifer C. Perry (Behavioral Ecology and Sociobiology, 2021)
Aggressive behaviours occur throughout the animal kingdom and agonistic contests often govern access to resources. Nutrition experienced during development has the potential to influence aggressive behaviours in adults through effects on growth, energy budgets and an individual’s internal state. In particular, resource-poor developmental nutrition might decrease adult aggression by limiting growth and energy budgets, or alternatively might increase adult aggression by enhancing motivation to compete for resources. However, the direction of this relationship—and effects of developmental nutrition experienced by rivals—remains unknown in most species, limiting understanding of how early-life environments contribute to variation in aggression. We investigated these alternative hypotheses by assessing male-male aggression in adult fruit flies, Drosophila melanogaster , that developed on a low-, medium- or high-resource diet, manipulated via yeast content. We found that a low-resource developmental diet reduced the probability of aggressive lunges in adults, as well as threat displays against rivals that developed on a low-resource diet. These effects appeared to be independent of diet-related differences in body mass. Males performed relatively more aggression on a central food patch when facing rivals of a low-resource diet, suggesting that developmental diet affects aggressive interactions through social effects in addition to individual effects. Our finding that resource-poor developmental diets reduce male-male aggression in D. melanogaster is consistent with the idea that resource budgets mediate aggression and in a mass-independent manner. Our study improves understanding of the links between nutrition and aggression. Significance statement Early-life nutrition can influence social behaviours in adults. Aggression is a widespread social behaviour with important consequences for fitness. Using the fruit fly, Drosophila melanogaster , we show that a poor developmental diet reduces aspects of adult aggressive behaviour in males. Furthermore, males perform more aggression near food patches when facing rivals of poor nutrition. This suggests that early-life nutrition affects aggressive interactions through social effects in addition to individual effects.

Diffusion MRI as a complementary assessment to cognition, emotion, and motor dysfunction after sports-related concussion: a systematic review and critical appraisal of the literature - Sarah C. Hellewell; Thomas Welton; Alan J. Pearce; Jerome J. Maller; Stuart M. Grieve (Brain Imaging and Behavior, 2021)

Sexual Mismatch Between Vessel-Associated Foraging and Discard Consumption in a Marine Top Predator - Joan Giménez; Gavin E. Arneill; Ashley Bennison; Enrico Pirotta; Hans D. Gerritsen; Thomas W. Bodey; Stuart Bearhop; Keith C. Hamer; Stephen Votier; Mark Jessopp (Frontiers in Marine Science, 2021)
Sex differences in diet and foraging behaviour are common in sexually dimorphic species, often driven by differences in the cost of locomotion or ability to exploit different ecological niches. However, sex-specific foraging strategies also occur in monomorphic or slightly dimorphic species where the drivers are poorly understood. Here, we study sex differences in foraging of northern gannets ( Morus bassanus ), where females are only slightly heavier than males. Using concurrently tracked gannets (298 full foraging trips from 81 individuals) and fishing vessels across 5 years, we quantify individual-based vessel-associated putative foraging, and relate this to discard consumption. We found a significant positive relationship between time spent in vessel-associated foraging and discard consumption for both sexes. However, while females showed greater proportions of vessel-associated foraging than males, discarded fish contributed less to the diet of females in all years. These results contrast with previous suggestions that female gannets interact with vessels less often than males, and are consistent with competitive exclusion of females from trawler-associated discards. Our findings give insight into sexual differences in foraging behaviour in the absence of dimorphism that are necessary to predict their response to environmental and anthropogenic changes.

Host Identity as a Driver of Moss-Associated N2 Fixation Rates in Alaska - Julia E. M. Stuart; Hannah Holland-Moritz; Lily R. Lewis; Mélanie Jean; Samantha N. Miller; Stuart F. McDaniel; Noah Fierer; José Miguel Ponciano; Michelle C. Mack (Ecosystems, 2021)

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Signatures of selection in a recent invasion reveal adaptive divergence in a highly vagile invasive species - Katarina C. Stuart; Adam P. A. Cardilini; Phillip Cassey; Mark F. Richardson; William B. Sherwin; Lee A. Rollins; Craig D. H. Sherman (Molecular Ecology, 2021)
A detailed understanding of population genetics in invasive populations helps us to identify drivers of successful alien introductions. Here, we investigate putative signals of selection in Australian populations of invasive common starlings, Sturnus vulgaris , and seek to understand how these have been influenced by introduction history. We used reduced representation sequencing to determine population structure, and identify Single Nucleotide Polymorphisms (SNPs) that are putatively under selection. We found that since their introduction into Australia, starling populations have become genetically differentiated despite the potential for high levels of dispersal, and that starlings have responded to selective pressures imposed by a wide range of environmental conditions across their geographic range. Isolation by distance appears to have played a strong role in determining genetic substructure across the starling's Australian range. Analyses of candidate SNPs that are putatively under selection indicated that aridity, precipitation and temperature may be important factors driving adaptive variation across the starling's invasive range in Australia. However, we also noted that the historic introduction regime may leave footprints on sites flagged as being under adaptive selection, and encourage critical interpretation of selection analyses in non‐native populations.

Novel Coating Uniformity Models for Tablet Pan Coaters - Michael Choi; Stuart C. Porter; Betsy Macht; Axel Meisen (AAPS PharmSciTech, 2021)

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

3D Bioprinting the Cardiac Purkinje System Using Human Adipogenic Mesenchymal Stem Cell Derived Purkinje Cells - Evan P. Tracy; Brian C. Gettler; Joseph S. Zakhari; Robert J. Schwartz; Stuart K. Williams; Ravi K. Birla (Cardiovascular Engineering and Technology, 2020)

Time-Dynamic Food Web Modeling to Explore Environmental Drivers of Ecosystem Change on the Kerguelen Plateau - Roshni C. Subramaniam; Jessica Melbourne-Thomas; Stuart P. Corney; Karen Alexander; Clara Péron; Philippe Ziegler; Kerrie M. Swadling (Frontiers in Marine Science, 2020)

Tiered analysis of whole-exome sequencing for epilepsy diagnosis - Paul J. Dunn; Bridget H. Maher; Cassie L. Albury; Shani Stuart; Heidi G. Sutherland; Neven Maksemous; Miles C. Benton; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2020)

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Long-term trends in albatross diets in relation to prey availability and breeding success - William F. Mills; José C. Xavier; Stuart Bearhop; Yves Cherel; Stephen C. Votier; Claire M. Waluda; Richard A. Phillips (Marine Biology, 2020)

Testing for changes in biomass dynamics in large‐scale forest datasets - Ervan Rutishauser; Stuart J. Wright; Richard Condit; Stephen P. Hubbell; Stuart J. Davies; Helene C. Muller‐Landau (Global Change Biology, 2020)
Tropical forest responses to climate and atmospheric change are critical to the future of the global carbon budget. Recent studies have reported increases in estimated above‐ground biomass (EAGB) stocks, productivity, and mortality in old‐growth tropical forests. These increases could reflect a shift in forest functioning due to global change and/or long‐lasting recovery from past disturbance. We introduce a novel approach to disentangle the relative contributions of these mechanisms by decomposing changes in whole‐plot biomass fluxes into contributions from changes in the distribution of gap‐successional stages and changes in fluxes for a given stage. Using 30 years of forest dynamic data at Barro Colorado Island, Panama, we investigated temporal variation in EAGB fluxes as a function of initial EAGB (EAGB i ) in 10 × 10 m quadrats. Productivity and mortality fluxes both increased strongly with initial quadrat EAGB. The distribution of EAGB (and thus EAGB i ) across quadrats hardly varied over 30 years (and seven censuses). EAGB fluxes as a function of EAGB i varied largely and significantly among census intervals, with notably higher productivity in 1985–1990 associated with recovery from the 1982–1983 El Niño event. Variation in whole‐plot fluxes among census intervals was explained overwhelmingly by variation in fluxes as a function of EAGB i , with essentially no contribution from changes in EAGB i distributions. The high observed temporal variation in productivity and mortality suggests that this forest is very sensitive to climate variability. There was no consistent long‐term trend in productivity, mortality, or biomass in this forest over 30 years, although the temporal variability in productivity and mortality was so strong that it could well mask a substantial trend. Accurate prediction of future tropical forest carbon budgets will require accounting for disturbance‐recovery dynamics and understanding temporal variability in productivity and mortality.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Using time-series similarity measures to compare animal movement trajectories in ecology - Ian R. Cleasby; Ewan D. Wakefield; Barbara J. Morrissey; Thomas W. Bodey; Steven C. Votier; Stuart Bearhop; Keith C. Hamer (Behavioral Ecology and Sociobiology, 2019)
Identifying and understanding patterns in movement data are amongst the principal aims of movement ecology. By quantifying the similarity of movement trajectories, inferences can be made about diverse processes, ranging from individual specialisation to the ontogeny of foraging strategies. Movement analysis is not unique to ecology however, and methods for estimating the similarity of movement trajectories have been developed in other fields but are currently under-utilised by ecologists. Here, we introduce five commonly used measures of trajectory similarity: dynamic time warping (DTW), longest common subsequence (LCSS), edit distance for real sequences (EDR), Fréchet distance and nearest neighbour distance (NND), of which only NND is routinely used by ecologists. We investigate the performance of each of these measures by simulating movement trajectories using an Ornstein-Uhlenbeck (OU) model in which we varied the following parameters: (1) the point of attraction, (2) the strength of attraction to this point and (3) the noise or volatility added to the movement process in order to determine which measures were most responsive to such changes. In addition, we demonstrate how these measures can be applied using movement trajectories of breeding northern gannets ( Morus bassanus ) by performing trajectory clustering on a large ecological dataset. Simulations showed that DTW and Fréchet distance were most responsive to changes in movement parameters and were able to distinguish between all the different parameter combinations we trialled. In contrast, NND was the least sensitive measure trialled. When applied to our gannet dataset, the five similarity measures were highly correlated despite differences in their underlying calculation. Clustering of trajectories within and across individuals allowed us to easily visualise and compare patterns of space use over time across a large dataset. Trajectory clusters reflected the bearing on which birds departed the colony and highlighted the use of well-known bathymetric features. As both the volume of movement data and the need to quantify similarity amongst animal trajectories grow, the measures described here and the bridge they provide to other fields of research will become increasingly useful in ecology. Significance statement As the use of tracking technology increases, there is a need to develop analytical techniques to process such large volumes of data. One area in which this would be useful is the comparison of individual movement trajectories. In response, a variety of measures of trajectory similarity have been developed within the information sciences. However, such measures are rarely used by ecologists who may be unaware of them. To remedy this, we apply five common measures of trajectory similarity to both simulated data and real ecological dataset comprising of movement trajectories of breeding northern gannets. Dynamic time warping and Fréchet distance performed best on simulated data. Using trajectory similarity measures on our gannet dataset, we identified distinct foraging clusters centred on different bathymetric features, demonstrating one application of such similarity measures. As new technology and analysis techniques proliferate across ecology and the information sciences, closer ties between these fields promise further innovative analysis of movement data.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Redmap Australia: Challenges and Successes With a Large-Scale Citizen Science-Based Approach to Ecological Monitoring and Community Engagement on Climate Change - Gretta T. Pecl; Jemina Stuart-Smith; Peter Walsh; Dianne J. Bray; Martha Kusetic; Michael Burgess; Stewart D. Frusher; Daniel C. Gledhill; Oliver George; Gary Jackson; John Keane; Victoria Y. Martin; et al. (Frontiers in Marine Science, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Elastic-Softening-Plasticity Around a Borehole: An Analytical and Experimental Study - Adelina Lv; Hossein Masoumi; Stuart D. C. Walsh; Hamid Roshan (Rock Mechanics and Rock Engineering, 2019)

Genetic modification of western wheatgrass (Pascopyrum smithii) for the phytoremediation of RDX and TNT - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Planta, 2019)

Using IUCN criteria to perform rapid assessments of at-risk taxa - Tom D. Le Breton; Heidi C. Zimmer; Rachael V. Gallagher; Michelle Cox; Stuart Allen; Tony D. Auld (Biodiversity and Conservation, 2019)

Body size, reef area and temperature predict global reef‐fish species richness across spatial scales - D. R. Barneche; E. L. Rezende; V. Parravicini; E. Maire; G. J. Edgar; R. D. Stuart‐Smith; J. E. Arias‐González; C. E. L. Ferreira; A. M. Friedlander; A. L. Green; O. J. Luiz; F. A. Rodríguez‐Zaragoza; et al. (Global Ecology and Biogeography, 2019)
Aim To investigate biotic and abiotic correlates of reef‐fish species richness across multiple spatial scales. Location Tropical reefs around the globe, including 485 sites in 109 sub‐provinces spread across 14 biogeographic provinces. Time period Present. Major taxa studied 2,523 species of reef fish. Methods We compiled a database encompassing 13,050 visual transects. We used hierarchical linear Bayesian models to investigate whether fish body size, reef area, isolation, temperature, and anthropogenic impacts correlate with reef‐fish species richness at each spatial scale (i.e., sites, sub‐provinces, provinces). Richness was estimated using coverage‐based rarefaction. We also tested whether species packing (i.e., transect‐level species richness/m 2 ) is correlated with province‐level richness. Results Body size had the strongest effect on species richness across all three spatial scales. Reef area and temperature were both positively correlated with richness at all spatial scales. At the site scale only, richness decreased with reef isolation. Species richness was not correlated with proxies of human impacts. Species packing was correlated with species richness at the province level following a sub‐linear power function. Province‐level differences in species richness were also mirrored by patterns of body size distribution at the site scale. Species‐rich provinces exhibited heterogeneous assemblages of small‐bodied species with small range sizes, whereas species‐poor provinces encompassed homogeneous assemblages composed by larger species with greater dispersal capacity. Main conclusions Our findings suggest that body size distribution, reef area and temperature are major predictors of species richness and accumulation across scales, consistent with recent theories linking home range to species–area relationships as well as metabolic effects on speciation rates. Based on our results, we hypothesize that in less diverse areas, species are larger and likely more dispersive, leading to larger range sizes and less turnover between sites. Our results indicate that changes in province‐level (i.e., regional) richness should leave a tractable fingerprint in local assemblages, and that detailed studies on local‐scale assemblage composition may be informative of responses occurring at larger scales.

Incorporating social dimensions in planning, managing and evaluating environmental projects - C. Louise Goggin; Thomas Barrett; John Leys; Gregory Summerell; Emma Gorrod; Stuart Waters; Mark Littleboy; Tony D. Auld; Michael J. Drielsma; Brian R. Jenkins (Environmental Management, 2019)

Seasonal and Long-Term Dynamics in Stream Water Sodium Chloride Concentrations and the Effectiveness of Road Salt Best Management Practices - Victoria R. Kelly; Stuart E. Findlay; Stephen K. Hamilton; Gary M. Lovett; Kathleen C. Weathers (Water, Air, & Soil Pollution, 2019)

Spawning patterns provide further evidence for multiple stocks of sardine ( Sardinops sagax ) off eastern Australia - Stuart C. Sexton; Tim M. Ward; John Stewart; Kerrie M. Swadling; Charlie Huveneers (Fisheries Oceanography, 2019)
Previous studies have suggested that sardine, Sardinops sagax , off eastern Australia spawns across its entire range when habitat conditions are suitable. However, recent studies have suggested that separate sub‐populations and spawning groups may occur in the region. Spawning patterns off eastern Australia were investigated using data collected during nine ichthyoplankton surveys conducted between 1997–2015, and adult reproductive data obtained from ad hoc commercial sampling off New South Wales ( NSW ). The egg surveys covered the known distribution of sardine off eastern Australia and included year‐round sampling in the northern and southern parts of this range. Egg distributions and analysis of gonadosomatic indices identified two spatio‐temporally separate spawning groups; one occurring off southern Queensland to northern NSW during late winter and early spring, and a smaller group off eastern Tasmania to southern NSW during summer. Most eggs were collected from waters 50–90 m deep, with sea surface temperatures of 18–23°C. Additive modelling indicated depth was the most significant factor driving selection of spawning habitat, followed by the interaction of month and latitude. Low egg densities were recorded in waters between 34–37°S, despite conditions within the ranges suitable for spawning. The presence of two spawning groups of sardine off eastern Australia supports recent findings that two sub‐populations occur in the region. Findings of this study will help to optimise the spatio‐temporal extent of future egg surveys and further confirm the need to coordinate future management of each sub‐population among relevant jurisdictions.

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Resistance training in young men induces muscle transcriptome-wide changes associated with muscle structure and metabolism refining the response to exercise-induced stress - Felipe Damas; Carlos Ugrinowitsch; Cleiton A. Libardi; Paulo R. Jannig; Amy J. Hector; Chris McGlory; Manoel E. Lixandrão; Felipe C. Vechin; Horacio Montenegro; Valmor Tricoli; Hamilton Roschel; Stuart M. Phillips (European Journal of Applied Physiology, 2018)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Terrestrial species adapted to sea dispersal: Differences in propagule dispersal of two Caribbean mangroves - Richard G. J. Hodel; L. Lacey Knowles; Stuart F. McDaniel; Adam C. Payton; Jordan F. Dunaway; Pamela S. Soltis; Douglas E. Soltis (Molecular Ecology, 2018)
A central goal of comparative phylogeography is to understand how species‐specific traits interact with geomorphological history to govern the geographic distribution of genetic variation within species. One key biotic trait with an immense impact on the spatial patterns of intraspecific genetic differentiation is dispersal. Here, we quantify how species‐specific traits directly related to dispersal affect genetic variation in terrestrial organisms with adaptations for dispersal by sea, not land—the mangroves of the Caribbean. We investigate the phylogeography of white mangroves ( Laguncularia racemosa , Combretaceae) and red mangroves ( Rhizophora mangle , Rhizophoraceae) using chloroplast genomes and nuclear markers (thousands of RAD ‐Seq loci) from individuals throughout the Caribbean. Both coastal tree species have viviparous propagules that can float in salt water for months, meaning they are capable of dispersing long distances. Spatially explicit tests of the role of ocean currents on patterning genetic diversity revealed that ocean currents act as a mechanism for facilitating dispersal, but other means of moving genetic material are also important. We measured pollen‐ vs. propagule‐mediated gene flow and discovered that in white mangroves, seeds were more important for promoting genetic connectivity between populations, but in red mangroves, the opposite was true: pollen contributed more. This result challenges our concept of the importance of both proximity to ocean currents for moving mangrove seeds and the extent of long‐distance pollen dispersal. This study also highlights the importance of spatially explicit quantification of both abiotic (ocean currents) and biotic (dispersal) factors contributing to gene flow to understand fully the phylogeographic histories of species.

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

The Impact of Federal and State Conservation Programs on Farmer Nitrogen Management - Adam P. Reimer; Riva C. H. Denny; Diana Stuart (Environmental Management, 2018)

Presence of a generalist entomopathogenic fungus influences the oviposition behaviour of an aphid-specific predator - A. G. C. de Azevedo; R. M. Stuart; L. Sigsgaard (BioControl, 2018)

3D human liver tissue from pluripotent stem cells displays stable phenotype in vitro and supports compromised liver function in vivo - Hassan Rashidi; Nguyet-Thin Luu; Salamah M. Alwahsh; Maaria Ginai; Sharmin Alhaque; Hua Dong; Rute A. Tomaz; Bertrand Vernay; Vasanthy Vigneswara; John M. Hallett; Anil Chandrashekran; Anil Dhawan; et al. (Archives of Toxicology, 2018)

Economic evaluation of micafungin versus liposomal amphotericin B (LAmB) for treating patients with candidaemia and invasive candidiasis (IC) in Turkey - Chin Fen Neoh; Esin Senol; Ates Kara; Ener Cagri Dinleyici; Stuart J. Turner; David C. M. Kong (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

These aren’t the loci you’e looking for: Principles of effective SNP filtering for molecular ecologists - Shannon J. O'Leary; Jonathan B. Puritz; Stuart C. Willis; Christopher M. Hollenbeck; David S. Portnoy (Molecular Ecology, 2018)
Sequencing reduced‐representation libraries of restriction site‐associated DNA ( RAD seq) to identify single nucleotide polymorphisms ( SNP s) is quickly becoming a standard methodology for molecular ecologists. Because of the scale of RAD seq data sets, putative loci cannot be assessed individually, making the process of filtering noise and correctly identifying biologically meaningful signal more difficult. Artefacts introduced during library preparation and/or bioinformatic processing of SNP data can create patterns that are incorrectly interpreted as indicative of population structure or natural selection. Therefore, it is crucial to carefully consider types of errors that may be introduced during laboratory work and data processing, and how to minimize, detect and remove these errors. Here, we discuss issues inherent to RAD seq methodologies that can result in artefacts during library preparation and locus reconstruction resulting in erroneous SNP calls and, ultimately, genotyping error. Further, we describe steps that can be implemented to create a rigorously filtered data set consisting of markers accurately representing independent loci and compare the effect of different combinations of filters on four RAD data sets. At last, we stress the importance of publishing raw sequence data along with final filtered data sets in addition to detailed documentation of filtering steps and quality control measures.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Novel bacterial lineages associated with boreal moss species - Hannah Holland‐Moritz; Julia Stuart; Lily R. Lewis; Samantha Miller; Michelle C. Mack; Stuart F. McDaniel; Noah Fierer (Environmental Microbiology, 2018)
Summary Mosses are critical components of boreal ecosystems where they typically account for a large proportion of net primary productivity and harbour diverse bacterial communities that can be the major source of biologically‐fixed nitrogen in these ecosystems. Despite their ecological importance, we have limited understanding of how microbial communities vary across boreal moss species and the extent to which local site conditions may influence the composition of these bacterial communities. We used marker gene sequencing to analyze bacterial communities associated with seven boreal moss species collected near Fairbanks, AK, USA. We found that host identity was more important than site in determining bacterial community composition and that mosses harbour diverse lineages of potential N 2 ‐fixers as well as an abundance of novel taxa assigned to understudied bacterial phyla (including candidate phylum WPS‐2). We performed shotgun metagenomic sequencing to assemble genomes from the WPS‐2 candidate phylum and found that these moss‐associated bacteria are likely anoxygenic phototrophs capable of carbon fixation via RuBisCo with an ability to utilize byproducts of photorespiration from hosts via a glyoxylate shunt. These results give new insights into the metabolic capabilities of understudied bacterial lineages that associate with mosses and the importance of plant hosts in shaping their microbiomes.

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

Impact of multiple stressors on juvenile fish in estuaries of the northeast Pacific - Jason D. Toft; Stuart H. Munsch; Jeffery R. Cordell; Kiira Siitari; Van C. Hare; Brett M. Holycross; Lisa A. DeBruyckere; Correigh M. Greene; Brent B. Hughes (Global Change Biology, 2018)
A key step in identifying global change impacts on species and ecosystems is to quantify effects of multiple stressors. To date, the science of global change has been dominated by regional field studies, experimental manipulation, meta‐analyses, conceptual models, reviews, and studies focusing on a single stressor or species over broad spatial and temporal scales. Here, we provide one of the first studies for coastal systems examining multiple stressor effects across broad scales, focused on the nursery function of 20 estuaries spanning 1,600 km of coastline, 25 years of monitoring, and seven fish and invertebrate species along the northeast Pacific coast. We hypothesized those species most estuarine dependent and negatively impacted by human activities would have lower presence and abundances in estuaries with greater anthropogenic land cover, pollution, and water flow stress. We found significant negative relationships between juveniles of two of seven species (Chinook salmon and English sole) and estuarine stressors. Chinook salmon were less likely to occur and were less abundant in estuaries with greater pollution stress. They were also less abundant in estuaries with greater flow stress, although this relationship was marginally insignificant. English sole were less abundant in estuaries with greater land cover stress. Together, we provide new empirical evidence that effects of stressors on two fish species culminate in detectable trends along the northeast Pacific coast, elevating the need for protection from pollution, land cover, and flow stressors to their habitats. Lack of response among the other five species could be related to differing resistance to specific stressors, type and precision of the stressor metrics, and limitations in catch data across estuaries and habitats. Acquiring improved measurements of impacts to species will guide future management actions, and help predict how estuarine nursery functions can be optimized given anthropogenic stressors and climate change scenarios.

Biophysical drivers of coral trophic depth zonation - Gareth J. Williams; Stuart A. Sandin; Brian J. Zgliczynski; Michael D. Fox; Jamison M. Gove; Justin S. Rogers; Kathryn A. Furby; Aaron C. Hartmann; Zachary R. Caldwell; Nichole N. Price; Jennifer E. Smith (Marine Biology, 2018)

Why decadal to century timescale palaeoclimate data are needed to explain present‐day patterns of biological diversity and change - Damien A. Fordham; Frédérik Saltré; Stuart C. Brown; Camille Mellin; Tom M. L. Wigley (Global Change Biology, 2018)
The current distribution of species, environmental conditions and their interactions represent only one snapshot of a planet that is continuously changing, in part due to human influences. To distinguish human impacts from natural factors, the magnitude and pace of climate shifts, since the Last Glacial Maximum, are often used to determine whether patterns of diversity today are artefacts of past climate change. In the absence of high‐temporal resolution palaeoclimate reconstructions, this is generally done by assuming that past climate change occurred at a linear pace between widely spaced (usually, ≥1,000 years) climate snapshots. We show here that this is a flawed assumption because regional climates have changed significantly across decades and centuries during glacial–interglacial cycles, likely causing rapid regional replacement of biota. We demonstrate how recent atmosphere‐ocean general circulation model ( AOGCM ) simulations of the climate of the past 21,000 years can provide credible estimates of the details of climate change on decadal to centennial timescales, showing that these details differ radically from what might be inferred from longer timescale information. High‐temporal resolution information can provide more meaningful estimates of the magnitude and pace of climate shifts, the location and timing of drivers of physiological stress, and the extent of novel climates. They also produce new opportunities to directly investigate whether short‐term climate variability is more important in shaping biodiversity patterns rather than gradual changes in long‐term climatic means. Together, these more accurate measures of past climate instability are likely to bring about a better understanding of the role of palaeoclimatic change and variability in shaping current macroecological patterns in many regions of the world.

How complex should models be? Comparing correlative and mechanistic range dynamics models - Damien A. Fordham; Cleo Bertelsmeier; Barry W. Brook; Regan Early; Dora Neto; Stuart C. Brown; Sébastien Ollier; Miguel B. Araújo (Global Change Biology, 2018)
Criticism has been levelled at climate‐change‐induced forecasts of species range shifts that do not account explicitly for complex population dynamics. The relative importance of such dynamics under climate change is, however, undetermined because direct tests comparing the performance of demographic models vs. simpler ecological niche models are still lacking owing to difficulties in evaluating forecasts using real‐world data. We provide the first comparison of the skill of coupled ecological‐niche‐population models and ecological niche models in predicting documented shifts in the ranges of 20 British breeding bird species across a 40‐year period. Forecasts from models calibrated with data centred on 1970 were evaluated using data centred on 2010. We found that more complex coupled ecological‐niche‐population models (that account for dispersal and metapopulation dynamics) tend to have higher predictive accuracy in forecasting species range shifts than structurally simpler models that only account for variation in climate. However, these better forecasts are achieved only if ecological responses to climate change are simulated without static snapshots of historic land use, taken at a single point in time. In contrast, including both static land use and dynamic climate variables in simpler ecological niche models improve forecasts of observed range shifts. Despite being less skilful at predicting range changes at the grid‐cell level, ecological niche models do as well, or better, than more complex models at predicting the magnitude of relative change in range size. Therefore, ecological niche models can provide a reasonable first approximation of the magnitude of species' potential range shifts, especially when more detailed data are lacking on dispersal dynamics, demographic processes underpinning population performance, and change in land cover.

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Visitor Preferences for Visual Changes in Bark Beetle-Impacted Forest Recreation Settings in the United States and Germany - Arne Arnberger; Martin Ebenberger; Ingrid E. Schneider; Stuart Cottrell; Alexander C. Schlueter; Eick von Ruschkowski; Robert C. Venette; Stephanie A. Snyder; Paul H. Gobster (Environmental Management, 2018)

Correction to: Comparison of Surface Properties in Natural and Artificially Generated Fractures in a Crystalline Rock - Daniel Vogler; Stuart D. C. Walsh; Peter Bayer; Florian Amann (Rock Mechanics and Rock Engineering, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

The interplay of climate and land use change affects the distribution of EU bumblebees - Leon Marshall; Jacobus C. Biesmeijer; Pierre Rasmont; Nicolas J. Vereecken; Libor Dvorak; Una Fitzpatrick; Frédéric Francis; Johann Neumayer; Frode Ødegaard; Juho P. T. Paukkunen; Tadeusz Pawlikowski; Menno Reemer; et al. (Global Change Biology, 2018)
Bumblebees in Europe have been in steady decline since the 1900s. This decline is expected to continue with climate change as the main driver. However, at the local scale, land use and land cover ( LULC ) change strongly affects the occurrence of bumblebees. At present, LULC change is rarely included in models of future distributions of species. This study's objective is to compare the roles of dynamic LULC change and climate change on the projected distribution patterns of 48 European bumblebee species for three change scenarios until 2100 at the scales of Europe, and Belgium, Netherlands and Luxembourg ( BENELUX ). We compared three types of models: (1) only climate covariates, (2) climate and static LULC covariates and (3) climate and dynamic LULC covariates. The climate and LULC change scenarios used in the models include, extreme growth applied strategy ( GRAS ), business as might be usual and sustainable European development goals. We analysed model performance, range gain/loss and the shift in range limits for all bumblebees. Overall, model performance improved with the introduction of LULC covariates. Dynamic models projected less range loss and gain than climate‐only projections, and greater range loss and gain than static models. Overall, there is considerable variation in species responses and effects were most pronounced at the BENELUX scale. The majority of species were predicted to lose considerable range, particularly under the extreme growth scenario ( GRAS ; overall mean: 64% ± 34). Model simulations project a number of local extinctions and considerable range loss at the BENELUX scale (overall mean: 56% ± 39). Therefore, we recommend species‐specific modelling to understand how LULC and climate interact in future modelling. The efficacy of dynamic LULC change should improve with higher thematic and spatial resolution. Nevertheless, current broad scale representations of change in major land use classes impact modelled future distribution patterns.

Infections Up to 76 Days After Stroke Increase Disability and Death - Annastazia E. Learoyd; Lisa Woodhouse; Laurence Shaw; Nikola Sprigg; Daniel Bereczki; Eivind Berge; Valeria Caso; Hanne Christensen; Ronan Collins; Anna Czlonkowska; Anwar El Etribi; Tracy D. Farr; et al. (Translational Stroke Research, 2017)

Large-area imaging reveals biologically driven non-random spatial patterns of corals at a remote reef - Clinton B. Edwards; Yoan Eynaud; Gareth J. Williams; Nicole E. Pedersen; Brian J. Zgliczynski; Arthur C. R. Gleason; Jennifer E. Smith; Stuart A. Sandin (Coral Reefs, 2017)

The Acoustic Habitat Hypothesis: An Ecoacoustics Perspective on Species Habitat Selection - Timothy C. Mullet; Almo Farina; Stuart H. Gage (Biosemiotics, 2017)

Comparison of Surface Properties in Natural and Artificially Generated Fractures in a Crystalline Rock - Daniel Vogler; Stuart D. C. Walsh; Peter Bayer; Florian Amann (Rock Mechanics and Rock Engineering, 2017)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Porites coral response to an oceanographic and human impact gradient in the Line Islands - Jessica E. Carilli; Aaron C. Hartmann; Scott F. Heron; John M. Pandolfi; Kim Cobb; Hussein Sayani; Robert Dunbar; Stuart A. Sandin (Limnology and Oceanography, 2017)
Coral bleaching caused by heat stress (warm water) will arguably be the greatest driver of coral reef loss in the coming decades. Understanding how corals have adapted to distinct oceanographic regimes on multiple scales can provide insight into future tolerance and persistence, information critical to directed intervention or targeted protections. The northern Line Islands span a gradient in oceanographic regimes across latitudes, with seawater becoming warmer, fresher, more oligotrophic, and more saturated with aragonite away from the equator. The combination of this regional gradient and island‐scale (local) conditions was used as a natural experiment against which to test how massive Porites corals respond to these background conditions and episodic heat stress. We found that coral condition, represented by a metric combining tissue thickness, lipids, and calcification, was similar at almost all islands, though there were differences in how corals allocate resources among these biological parameters. Corals at Teraina, the most densely inhabited island, showed evidence for reduced calcification, potentially associated with human impacts and/or outflow of freshwater from the island. In contrast, Porites corals at Palmyra, a wildlife reserve, exhibited unexpectedly high tissue‐condition metrics for its latitude, suggesting an additional food source, possibly plankton‐rich lagoonal outflow. We did not find a strong relationship between human habitation and the response of Porites corals to recent heat stress. However, differences in coral calcification rates and energy stores between observed values and those expected based solely on the regional oceanographic gradient, suggests local effects have indirect impacts on these corals.

Idiosyncratic responses to climate‐driven forest fragmentation and marine incursions in reed frogs from Central Africa and the Gulf of Guinea Islands - Rayna C. Bell; Juan L. Parra; Gabriel Badjedjea; Michael F. Barej; David C. Blackburn; Marius Burger; Alan Channing; Jonas Maximilian Dehling; Eli Greenbaum; Václav Gvoždík; Jos Kielgast; Chifundera Kusamba; et al. (Molecular Ecology, 2017)
Organismal traits interact with environmental variation to mediate how species respond to shared landscapes. Thus, differences in traits related to dispersal ability or physiological tolerance may result in phylogeographic discordance among co‐distributed taxa, even when they are responding to common barriers. We quantified climatic suitability and stability, and phylogeographic divergence within three reed frog species complexes across the Guineo‐Congolian forests and Gulf of Guinea archipelago of Central Africa to investigate how they responded to a shared climatic and geological history. Our species‐specific estimates of climatic suitability through time are consistent with temporal and spatial heterogeneity in diversification among the species complexes, indicating that differences in ecological breadth may partly explain these idiosyncratic patterns. Likewise, we demonstrated that fluctuating sea levels periodically exposed a land bridge connecting Bioko Island with the mainland Guineo‐Congolian forest and that habitats across the exposed land bridge likely enabled dispersal in some species, but not in others. We did not find evidence that rivers are biogeographic barriers across any of the species complexes. Despite marked differences in the geographic extent of stable climates and temporal estimates of divergence among the species complexes, we recovered a shared pattern of intermittent climatic suitability with recent population connectivity and demographic expansion across the Congo Basin. This pattern supports the hypothesis that genetic exchange across the Congo Basin during humid periods, followed by vicariance during arid periods, has shaped regional diversity. Finally, we identified many distinct lineages among our focal taxa, some of which may reflect incipient or unrecognized species.

Population density–range size relationship revisited - Maria Novosolov; Gordon H. Rodda; Alexandra C. North; Stuart H. M. Butchart; Oliver J. S. Tallowin; Alison M. Gainsbury; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim The species population density–range size relationship posits that locally abundant species are widely distributed. However, this proposed pattern has been insufficiently tested. The few tests conducted were usually limited in scale and gave conflicting results. We tested the generality of the positive population density–range size relationship. We then studied whether similar environmental niche requirements are correlated with range size and with population density to search for mechanisms driving the hypothesized link between population density and range size. Location Worldwide. Methods We collected data on population density, range size and environmental niche for a global dataset of 192 lizard, 893 bird and 350 mammal species. Assessing the relationship between population density and range size and environmental niche parameters, we corrected for phylogenetic relationships, body mass, diet and study area. Results Our findings reveal that density had a weak negative correlation with bird range size and was unrelated to lizard and mammal range size. These trends were consistent at the global scale and across the biogeographical realms. Range size was related to relatively similar environmental niche parameters in all groups. Population density, however, was explained by taxon‐specific factors and was therefore unrelated to range size by common causation. Main conclusions We suggest that the positive relationship between population density and range size identified in previous studies might be an artefact arising through incomplete sampling of range sizes. Our results indicate that the mechanisms shaping population density and range size may be independent.

Sleeper cells: the stringent response and persistence in the Borreliella ( Borrelia ) burgdorferi enzootic cycle - Felipe C. Cabello; Henry P. Godfrey; Julia V. Bugrysheva; Stuart A. Newman (Environmental Microbiology, 2017)
Summary Infections with tick‐transmitted Borreliella ( Borrelia ) burgdorferi , the cause of Lyme disease, represent an increasingly large public health problem in North America and Europe. The ability of these spirochetes to maintain themselves for extended periods of time in their tick vectors and vertebrate reservoirs is crucial for continuance of the enzootic cycle as well as for the increasing exposure of humans to them. The stringent response mediated by the alarmone (p)ppGpp has been determined to be a master regulator in B . burgdorferi . It modulates the expression of identified and unidentified open reading frames needed to deal with and overcome the many nutritional stresses and other challenges faced by the spirochete in ticks and animal reservoirs. The metabolic and morphologic changes resulting from activation of the stringent response in B . burgdorferi may also be involved in the recently described non‐genetic phenotypic phenomenon of tolerance to otherwise lethal doses of antimicrobials and to other antimicrobial activities. It may thus constitute a linchpin in multiple aspects of infections with Lyme disease borrelia, providing a link between the micro‐ecological challenges of its enzootic life‐cycle and long‐term residence in the tissues of its animal reservoirs, with the evolutionary side effect of potential persistence in incidental human hosts.

Drought‐induced mortality patterns and rapid biomass recovery in a terra firme forest in the Colombian Amazon - Daniel Zuleta; Alvaro Duque; Dairon Cardenas; Helene C. Muller‐Landau; Stuart J. Davies (Ecology, 2017)
Extreme climatic events affecting the Amazon region are expected to become more frequent under ongoing climate change. In this study, we assessed the responses to the 2010 drought of over 14,000 trees ≥10 cm dbh in a 25 ha lowland forest plot in the Colombian Amazon and how these responses varied among topographically defined habitats, with tree size, and with species wood density. Tree mortality was significantly higher during the 2010–2013 period immediately after the drought than in 2007–2010. The post‐drought increase in mortality was stronger for trees located in valleys (+243%) than for those located on slopes (+67%) and ridges (+57%). Tree‐based generalized linear mixed models showed a significant negative effect of species wood density on mortality and no effect of tree size. Despite the elevated post‐drought mortality, aboveground biomass increased from 2007 to 2013 by 1.62 Mg ha −1 yr −1 (95% CI 0.80–2.43 Mg ha −1 yr −1 ). Biomass change varied among habitats, with no significant increase on the slopes (1.05, 95% CI −0.76 to 2.85 Mg ha −1 yr −1 ), a significant increase in the valleys (1.33, 95% CI 0.37–2.34 Mg ha −1 yr −1 ), and a strong increase on the ridges (2.79, 95% CI 1.20–4.21 Mg ha −1 yr −1 ). These results indicate a high carbon resilience of this forest to the 2010 drought due to habitat‐associated and interspecific heterogeneity in responses including directional changes in functional composition driven by enhanced performance of drought‐tolerant species that inhabit the drier ridges.

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

Phytodetoxification of TNT by transplastomic tobacco (Nicotiana tabacum) expressing a bacterial nitroreductase - Long Zhang; Elizabeth L. Rylott; Neil C. Bruce; Stuart E. Strand (Plant Molecular Biology, 2017)

Microtubule-Targeting Agents Eribulin and Paclitaxel Differentially Affect Neuronal Cell Bodies in Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Krystyna M. Wozniak; Bridget Kulesh; April Savage; Barbara S. Slusher; Bruce A. Littlefield; Mary Ann Jordan; Leslie Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2017)

Urban groundwater quality in sub-Saharan Africa: current status and implications for water security and public health - D. J. Lapworth; D. C. W. Nkhuwa; J. Okotto-Okotto; S. Pedley; M. E. Stuart; M. N. Tijani; J. Wright (Hydrogeology Journal, 2017)

Integrated approach to determining stock structure: implications for fisheries management of sardine, Sardinops sagax, in Australian waters - Christopher Izzo; Tim M. Ward; Alex R. Ivey; Iain M. Suthers; John Stewart; Stuart C. Sexton; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2017)

Mechanisms driving Antarctic microbial community responses to ocean acidification: a network modelling approach - Roshni C. Subramaniam; Jessica Melbourne-Thomas; Andrew T. Davidson; Stuart P. Corney (Polar Biology, 2017)

Insights into regional patterns of Amazonian forest structure, diversity, and dominance from three large terra-firme forest dynamics plots - Alvaro Duque; Helene C. Muller-Landau; Renato Valencia; Dairon Cardenas; Stuart Davies; Alexandre de Oliveira; Álvaro J. Pérez; Hugo Romero-Saltos; Alberto Vicentini (Biodiversity and Conservation, 2017)

Population genetic structure of the Amazonian black flannelmouth characin (Characiformes, Prochilodontidae: Prochilodus nigricans Spix & Agassiz, 1829): contemporary and historical gene flow of a migratory and abundant fishery species - Valéria Nogueira Machado; Stuart C. Willis; Aylton S. Teixeira; Tomas Hrbek; Izeni Pires Farias (Environmental Biology of Fishes, 2017)

Numerical and Experimental Studies of Particle Settling in Real Fracture Geometries - Pratanu Roy; Wyatt L. Du Frane; Yuliya Kanarska; Stuart D. C. Walsh (Rock Mechanics and Rock Engineering, 2016)

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

Weighting and indirect effects identify keystone species in food webs - Lei Zhao; Huayong Zhang; Eoin J. O'Gorman; Wang Tian; Athen Ma; John C. Moore; Stuart R. Borrett; Guy Woodward (Ecology Letters, 2016)
Species extinctions are accelerating globally, yet the mechanisms that maintain local biodiversity remain poorly understood. The extinction of species that feed on or are fed on by many others (i.e. ‘hubs’) has traditionally been thought to cause the greatest threat of further biodiversity loss. Very little attention has been paid to the strength of those feeding links (i.e. link weight) and the prevalence of indirect interactions. Here, we used a dynamical model based on empirical energy budget data to assess changes in ecosystem stability after simulating the loss of species according to various extinction scenarios. Link weight and/or indirect effects had stronger effects on food‐web stability than the simple removal of ‘hubs’, demonstrating that both quantitative fluxes and species dissipating their effects across many links should be of great concern in biodiversity conservation, and the potential for ‘hubs’ to act as keystone species may have been exaggerated to date.

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Experimental whole‐lake increase of dissolved organic carbon concentration produces unexpected increase in crustacean zooplankton density - Patrick T. Kelly; Nicola Craig; Christopher T. Solomon; Brian C. Weidel; Jacob A. Zwart; Stuart E. Jones (Global Change Biology, 2016)
The observed pattern of lake browning, or increased terrestrial dissolved organic carbon ( DOC ) concentration, across the northern hemisphere has amplified the importance of understanding how consumer productivity varies with DOC concentration. Results from comparative studies suggest these increased DOC concentrations may reduce crustacean zooplankton productivity due to reductions in resource quality and volume of suitable habitat. Although these spatial comparisons provide an expectation for the response of zooplankton productivity as DOC concentration increases, we still have an incomplete understanding of how zooplankton respond to temporal increases in DOC concentration within a single system. As such, we used a whole‐lake manipulation, in which DOC concentration was increased from 8 to 11 mg L −1 in one basin of a manipulated lake, to test the hypothesis that crustacean zooplankton production should subsequently decrease. In contrast to the spatially derived expectation of sharp DOC ‐mediated decline, we observed a small increase in zooplankton densities in response to our experimental increase in DOC concentration of the treatment basin. This was due to significant increases in gross primary production and resource quality (lower seston carbon‐to‐phosphorus ratio; C:P). These results demonstrate that temporal changes in lake characteristics due to increased DOC may impact zooplankton in ways that differ from those observed in spatial surveys. We also identified significant interannual variability across our study region, which highlights potential difficulty in detecting temporal responses of organism abundances to gradual environmental change (e.g., browning).

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

Incorporating benthic community changes into hydrochemical-based projections of coral reef calcium carbonate production under ocean acidification - Emily C. Shaw; Sarah M. Hamylton; Stuart R. Phinn (Coral Reefs, 2016)

Growing older with health and vitality: a nexus of physical activity, exercise and nutrition - Oliver C. Witard; Chris McGlory; D. Lee Hamilton; Stuart M. Phillips (Biogerontology, 2016)

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

Cross-signaling in metabotropic glutamate 2 and serotonin 2A receptor heteromers in mammalian cells - Lia Baki; Miguel Fribourg; Jason Younkin; Jose Miguel Eltit; Jose L. Moreno; Gyu Park; Zhanna Vysotskaya; Adishesh Narahari; Stuart C. Sealfon; Javier Gonzalez-Maeso; Diomedes E. Logothetis (Pflügers Archiv - European Journal of Physiology, 2016)

Ecological Knowledge Among Communities, Managers and Scientists: Bridging Divergent Perspectives to Improve Forest Management Outcomes - Lucy Rist; Charlie Shackleton; Lily Gadamus; F. Stuart Chapin; C. Made Gowda; Siddappa Setty; Ramesh Kannan; R. Uma Shaanker (Environmental Management, 2016)

Thermal Drawdown-Induced Flow Channeling in Fractured Geothermal Reservoirs - Pengcheng Fu; Yue Hao; Stuart D. C. Walsh; Charles R. Carrigan (Rock Mechanics and Rock Engineering, 2016)

Phylogeography of the harvestman genus Metasiro (Arthropoda, Arachnida, Opiliones) reveals a potential solution to the Pangean paradox - Ronald M. Clouse; Prashant P. Sharma; Jessie C. Stuart; Lloyd R. Davis; Gonzalo Giribet; Sarah L. Boyer; Ward C. Wheeler (Organisms Diversity & Evolution, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

An inability to distinguish edematous swelling from true hypertrophy still prevents a completely accurate interpretation of the time course of muscle hypertrophy - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

Early resistance training-induced increases in muscle cross-sectional area are concomitant with edema-induced muscle swelling - Felipe Damas; Stuart M. Phillips; Manoel E. Lixandrão; Felipe C. Vechin; Cleiton A. Libardi; Hamilton Roschel; Valmor Tricoli; Carlos Ugrinowitsch (European Journal of Applied Physiology, 2016)

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

Are microbial communities in green roof substrates comparable to those in post-industrial sites?—a preliminary study - Chloe J. Molineux; Alan C. Gange; Stuart P. Connop; Darryl J. Newport (Urban Ecosystems, 2015)

Population genetics of the speckled peacock bass (Cichla temensis), South America’s most important inland sport fishery - Stuart C. Willis; Kirk O. Winemiller; Carmen G. Montaña; Jason Macrander; Paul Reiss; Izeni P. Farias; Guillermo Ortí (Conservation Genetics, 2015)

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

Structural Characterisation of Non-Deamidated Acidic Variants of Erwinia chrysanthemi L-asparaginase Using Small-Angle X-ray Scattering and Ion-Mobility Mass Spectrometry - David Gervais; Darryl King; Patrick Kanda; Nicholas Foote; Lucy Elliott; Phillip Brown; Natacha O. Lee; Konstantinos Thalassinos; Claire Pizzey; Robert Rambo; Thomas C. Minshull; Mark J. Dickman; et al. (Pharmaceutical Research, 2015)

Habitat, not resource availability, limits consumer production in lake ecosystems - Nicola Craig; Stuart E. Jones; Brian C. Weidel; Christopher T. Solomon (Limnology and Oceanography, 2015)
Food web productivity in lakes can be limited by dissolved organic carbon (DOC), which reduces fish production by limiting the abundance of their zoobenthic prey. We demonstrate that in a set of 10 small, north temperate lakes spanning a wide DOC gradient, these negative effects of high DOC concentrations on zoobenthos production are driven primarily by availability of warm, well‐oxygenated habitat, rather than by light limitation of benthic primary production as previously proposed. There was no significant effect of benthic primary production on zoobenthos production after controlling for oxygen, even though stable isotope analysis indicated that zoobenthos do use this resource. Mean whole‐lake zoobenthos production was lower in high‐DOC lakes with reduced availability of oxygenated habitat, as was fish biomass. These insights improve understanding of lake food webs and inform management in the face of spatial variability and ongoing temporal change in lake DOC concentrations.

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

Microbial biomass response to different quantities and sources of organic matter in B razilian coastal sediments - Cintia O. Quintana; Paula C. de Moraes; Marcos Y. Yoshinaga; Stuart G. Wakeham; Paulo Y. G. Sumida (Marine Ecology, 2015)
This study investigates the benthic microbial responses to organic matter ( OM ) variations in quantity and sources in two shallow water bays (Fortaleza and Ubatuba Bays) on the SE coast of Brazil on six occasions during the year. The pelagic and benthic compartments of the bays were evaluated by: (i) nutrients and chlorophyll a (Chl a ) in the water column; (ii) quantity and sources of OM in the sediment (Chl a , total organic carbon and total nitrogen and lipid biomarker composition); and (iii) microbial biomass in sediments as an indicator of active benthic response. Although there were changes in water‐column nutrients during the year, Chl a was fairly constant, suggesting a regular supply of microalgae‐derived OM to the sea bottom. Based on the composition of lipid biomarkers in sediments, OM sources were classified as mostly marine and with high contributions of labile (microalgae‐derived) OM . Labile OM composition varied from diatoms in the summer to phytoflagellates in the winter and tended to accumulate in areas protected by physical disturbances in one of the bays. Microbial biomass followed this trend and was 160% higher in protected than in exposed areas. This study suggests that the coupling between labile OM and benthic microbial biomass occurs primarily in protected areas, irrespective of the time of the year. Since meio‐ and macrofaunal assemblages depend upon secondary microbial production within the sediments, this coupling may have an important role for the benthic food‐web.

Genome‐wide association and genome partitioning reveal novel genomic regions underlying variation in gastrointestinal nematode burden in a wild bird - Marius A. Wenzel; Marianne C. James; Alex Douglas; Stuart B. Piertney (Molecular Ecology, 2015)
Identifying the genetic architecture underlying complex phenotypes is a notoriously difficult problem that often impedes progress in understanding adaptive eco‐evolutionary processes in natural populations. Host–parasite interactions are fundamentally important drivers of evolutionary processes, but a lack of understanding of the genes involved in the host's response to chronic parasite insult makes it particularly difficult to understand the mechanisms of host life history trade‐offs and the adaptive dynamics involved. Here, we examine the genetic basis of gastrointestinal nematode ( Trichostrongylus tenuis ) burden in 695 red grouse ( Lagopus lagopus scotica ) individuals genotyped at 384 genome‐wide SNPs. We first use genome‐wide association to identify individual SNPs associated with nematode burden. We then partition genome‐wide heritability to identify chromosomes with greater heritability than expected from gene content, due to harbouring a multitude of additive SNPs with individually undetectable effects. We identified five SNPs on five chromosomes that accounted for differences of up to 556 worms per bird, but together explained at best 4.9% of the phenotypic variance. These SNPs were closely linked to genes representing a range of physiological processes including the immune system, protein degradation and energy metabolism. Genome partitioning indicated genome‐wide heritability of up to 29% and three chromosomes with excess heritability of up to 4.3% (total 8.9%). These results implicate SNPs and novel genomic regions underlying nematode burden in this system and suggest that this phenotype is somewhere between being based on few large‐effect genes (oligogenic) and based on a large number of genes with small individual but large combined effects (polygenic).

Emplacement of the Cabezo María lamproite volcano (Miocene, SE Spain) - Thomas M. Gernon; Samuel Spence; Clive N. Trueman; Rex N. Taylor; Eelco Rohling; Stuart J. Hatter; Ian C. Harding (Bulletin of Volcanology, 2015)

Measuring coral size-frequency distribution using stereo video technology, a comparison with in situ measurements - Joseph A. Turner; Nicholas V. C. Polunin; Stuart N. Field; Shaun K. Wilson (Environmental Monitoring and Assessment, 2015)

Natural in situ relationships suggest coral reef calcium carbonate production will decline with ocean acidification - Emily C. Shaw; Stuart R. Phinn; Bronte Tilbrook; Andy Steven (Limnology and Oceanography, 2015)
There are few in situ studies showing how net community calcification ( G net ) of coral reefs is related to carbonate chemistry, and the studies to date have demonstrated different predicted rates of change. In this study, we measured net community production ( P net ), G net , and carbonate chemistry of a reef flat at One Tree Island, Great Barrier Reef. Diurnal p CO 2 variability of 289–724 μatm was driven primarily by photosynthesis and respiration. The reef flat was found to be net autotrophic, with daily production of ∼ 35 mmol C m −2 d −1 and net calcification of ∼ 33 mmol C m −2 d −1 . G net was strongly related to P net , which drove a hysteresis pattern in the relationship between G net and aragonite saturation state (Ω ar ). Although P net was the main driver of G net , Ω ar was still an important factor, where 95% of the variance in G net could be described by P net and Ω ar . Based on the observed in situ relationship, G net would be expected to reach zero when Ω ar is ∼ 2.5. It is unknown what proportion of a decline in G net would be through reduced calcification and what would occur through increased dissolution, but the results here support predictions that overall calcium carbonate production will decline in coral reefs as a result of ocean acidification.

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Ecosystem Consequences of Changing Inputs of Terrestrial Dissolved Organic Matter to Lakes: Current Knowledge and Future Challenges - Christopher T. Solomon; Stuart E. Jones; Brian C. Weidel; Ishi Buffam; Megan L. Fork; Jan Karlsson; Søren Larsen; Jay T. Lennon; Jordan S. Read; Steven Sadro; Jasmine E. Saros (Ecosystems, 2015)

Effect of a Medical Toxicology Admitting Service on Length of Stay, Cost, and Mortality Among Inpatients Discharged with Poisoning-Related Diagnoses - Steven C. Curry; Daniel E. Brooks; Aaron B. Skolnik; Richard D. Gerkin; Stuart Glenn (Journal of Medical Toxicology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Modeling of the Acute Effects of Primary Hypertension and Hypotension on the Hemodynamics of Intracranial Aneurysms - Ali Sarrami-Foroushani; Maria-Cruz Villa-Uriol; Mohsen Nasr Esfahany; Stuart C. Coley; Luigi Yuri Di Marco; Alejandro F. Frangi; Alberto Marzo (Annals of Biomedical Engineering, 2015)

Overseas dispersal of Hyperolius reed frogs from Central Africa to the oceanic islands of São Tomé and Príncipe - Rayna C. Bell; Robert C. Drewes; Alan Channing; Václav Gvoždík; Jos Kielgast; Stefan Lötters; Bryan L. Stuart; Kelly R. Zamudio (Journal of Biogeography, 2015)
Aim To infer the colonization history of reed frog species endemic to the oceanic islands of São Tomé and Príncipe, Hyperolius molleri and H. thomensis , we quantified phylogeographical structure in the closely related H. cinnamomeoventris species complex, which is broadly distributed across continental Central Africa. Location The Lower Guineo‐Congolian Forest and the Gulf of Guinea islands of São Tomé and Príncipe, Central Africa. Methods We combined gene and species tree analyses to investigate diversity and divergence among H. cinnamomeoventris populations, to identify the most likely dispersal route to the islands, and to infer the order in which the islands were colonized. One of the endemics ( H. molleri ) is distributed on both islands and we quantified genetic divergence between populations. Results We recovered three clades in H. cinnamomeoventris corresponding to West‐Central, North/East‐Central and South‐Central Africa. The island endemics form a monophyletic group most closely related to the West‐Central African H. cinnamomeoventris clade. Populations of H. molleri on São Tomé and Príncipe are reciprocally monophyletic at mitochondrial loci but nuclear gene trees do not support this divergence. Main conclusions Genetic structure in the H. cinnamomeoventris species complex coincides with biogeographical barriers identified in previous studies of Central African rain forest taxa. Individual gene tree and species tree analyses support a single dispersal event from the Ogooué or Congo river basins (West‐Central Africa) to the island of São Tomé, with subsequent divergence within São Tomé and dispersal to Príncipe.

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Linking the green and brown worlds: the prevalence and effect of multichannel feeding in food webs - Elizabeth M. Wolkovich; Stefano Allesina; Kathryn L. Cottingham; John C. Moore; Stuart A. Sandin; Claire de Mazancourt (Ecology, 2014)
Recent advances in food‐web ecology highlight that most real food webs (1) represent an interplay between producer‐ and detritus‐based webs and (2) are governed by consumers which are rampant omnivores; feeding on varied prey across trophic levels and resource channels. A possible avenue to unify these advances comes from models demonstrating that predators feeding on distinctly different channels may stabilize food webs. Empirical studies suggest many consumers engage in such behavior by feeding on prey items from both living‐autotroph (green) and detritus‐based (brown) webs, what we term “multichannel feeding,” yet we know little about how common such feeding is across systems and trophic levels, or its effect on system stability. Considering 23 empirical webs, we find that multichannel feeding is equally common across terrestrial, freshwater, and marine systems, with >50% of consumers classified as multichannel consumers. Multichannel feeding occurred most often at the first consumer level, indicating that most taxa at the herbivore/detritivore level are more aptly described as multichannel consumers, and that such feeding is not restricted to predators. We next developed a simple four‐compartment nutrient cycling model for consumers eating both autotrophs and detritus with separate parameter sets to represent aquatic vs. terrestrial ecosystems. Modeling results showed that, across terrestrial and aquatic ecosystems, multichannel feeding is stabilizing at low attack rates on autotrophs or when attack rates are asymmetric (moderate on autotrophs while low on detritus), but destabilizing at high attack rates on autotrophs, compared to herbivory‐ or detritivory‐only models. The set of conditions with stable webs with multichannel consumers is narrower, however, for aquatic systems, suggesting that multichannel feeding may generally be more stabilizing in terrestrial systems. Together, our results demonstrate that multichannel feeding is common across ecosystems and may be a stabilizing force in real webs that have consumers with low or asymmetric attack rates.

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

Early-phase musculoskeletal adaptations to different levels of eccentric resistance after 8 weeks of lower body training - Kirk L. English; James A. Loehr; Stuart M. C. Lee; Scott M. Smith (European Journal of Applied Physiology, 2014)

Dissolved organic carbon concentration controls benthic primary production: Results from in situ chambers in north‐temperate lakes - Sean C. Godwin; Stuart E. Jones; Brian C. Weidel; Christopher T. Solomon (Limnology and Oceanography, 2014)
We evaluated several potential drivers of primary production by benthic algae (periphyton) in north‐temperate lakes. We used continuous dissolved oxygen measurements from in situ benthic chambers to quantify primary production by periphyton at multiple depths across 11 lakes encompassing a broad range of dissolved organic carbon (DOC) and total phosphorous (TP) concentrations. Light‐use efficiency (primary production per unit incident light) was inversely related to average light availability (% of surface light) in 7 of the 11 study lakes, indicating that benthic algal assemblages exhibit photoadaptation, likely through physiological or compositional changes. DOC alone explained 86% of the variability in log‐transformed whole‐lake benthic production rates. TP was not an important driver of benthic production via its effects on nutrient and light availability. This result is contrary to studies in other systems, but may be common in relatively pristine north‐temperate lakes. Our simple empirical model may allow for the prediction of whole‐lake benthic primary production from easily obtained measurements of DOC concentration.

Predicting the likely response of data‐poor ecosystems to climate change using space‐for‐time substitution across domains - Rebecca E. Lester; Paul G. Close; Jan L. Barton; Adam J. Pope; Stuart C. Brown (Global Change Biology, 2014)
Predicting ecological response to climate change is often limited by a lack of relevant local data from which directly applicable mechanistic models can be developed. This limits predictions to qualitative assessments or simplistic rules of thumb in data‐poor regions, making management of the relevant systems difficult. We demonstrate a method for developing quantitative predictions of ecological response in data‐poor ecosystems based on a space‐for‐time substitution, using distant, well‐studied systems across an inherent climatic gradient to predict ecological response. Changes in biophysical data across the spatial gradient are used to generate quantitative hypotheses of temporal ecological responses that are then tested in a target region. Transferability of predictions among distant locations, the novel outcome of this method, is demonstrated via simple quantitative relationships that identify direct and indirect impacts of climate change on physical, chemical and ecological variables using commonly available data sources. Based on a limited subset of data, these relationships were demonstrably plausible in similar yet distant (>2000 km) ecosystems. Quantitative forecasts of ecological change based on climate‐ecosystem relationships from distant regions provides a basis for research planning and informed management decisions, especially in the many ecosystems for which there are few data. This application of gradient studies across domains – to investigate ecological response to climate change – allows for the quantification of effects on potentially numerous, interacting and complex ecosystem components and how they may vary, especially over long time periods (e.g. decades). These quantitative and integrated long‐term predictions will be of significant value to natural resource practitioners attempting to manage data‐poor ecosystems to prevent or limit the loss of ecological value. The method is likely to be applicable to many ecosystem types, providing a robust scientific basis for estimating likely impacts of future climate change in ecosystems where no such method currently exists.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Congenic mice reveal genetic epistasis and overlapping disease loci for autoimmune diabetes and listeriosis - Nancy Wang; Colleen M. Elso; Leanne Mackin; Stuart I. Mannering; Richard A. Strugnell; Odilia L. Wijburg; Thomas C. Brodnicki (Immunogenetics, 2014)

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Long-term copper partitioning of metal-spiked sediments used in outdoor mesocosms - Stephanie Gardham; Grant C. Hose; Stuart L. Simpson; Chad Jarolimek; Anthony A. Chariton (Environmental Science and Pollution Research, 2014)

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Terrestrial carbon is a resource, but not a subsidy, for lake zooplankton - Patrick T. Kelly; Christopher T. Solomon; Brian C. Weidel; Stuart E. Jones (Ecology, 2014)
Inputs of terrestrial organic carbon (t‐OC) into lakes are often considered a resource subsidy for aquatic consumer production. Although there is evidence that terrestrial carbon can be incorporated into the tissues of aquatic consumers, its ability to enhance consumer production has been debated. Our research aims to evaluate the net effect of t‐OC input on zooplankton. We used a survey of zooplankton production and resource use in ten lakes along a naturally occurring gradient of t‐OC concentration to address these questions. Total and group‐specific zooplankton production was negatively related to t‐OC. Residual variation in zooplankton production that was not explained by t‐OC was negatively related to terrestrial resource use (allochthony) by zooplankton. These results challenge the designation of terrestrial carbon as a resource subsidy; rather, the negative effect of reduced light penetration on the amount of suitable habitat and the low resource quality of t‐OC appear to diminish zooplankton production. Our findings suggest that ongoing continental‐scale increases in t‐OC concentrations of lakes will likely have negative impacts on the productivity of aquatic food webs.

Analysis of growth and stable isotopes in teeth of male Australian fur seals reveals interannual variability in prey resources - Travis C. Knox; Hilary Stuart‐Williams; Robert M. Warneke; Andrew J. Hoskins; John P. Y. Arnould (Marine Mammal Science, 2014)
To detect and monitor long‐term ecosystem responses to environmental variability, managers must utilize reliable and quantitative techniques to predict future ecosystem responses. Canine teeth from 67 male Australian fur seals (aged 2–19 yr), collected at Seal Rocks, between 1967 and 1976, were measured for relative growth within the dentine growth layer groups ( GLG s), as an index of body growth. Fluctuations in relative growth were apparent during 1956–1971, suggesting interannual variation in prey resources within Bass Strait. These were positively correlated with the Southern Oscillation Index and negatively with the Indian Ocean Subtropical Dipole, both on a 2 yr lag. The observed delay may reflect the time required for the nutrient cascade to filter through to the predominantly benthic prey of Australian fur seals. Stable isotope analysis ( δ 15 N/ δ 13 C) was also used to investigate whether fluctuations in growth were associated with differences in diet. Relative growth was found to be negatively correlated with δ 15 N, suggesting years of greater resource availability may be associated with individuals consuming proportionally more prey biomass of lower isotopic value. This study demonstrates that fluctuations in the dentine GLG s of male Australian fur seals are related to environmental parameters, suggesting variation in body growth is mediated by changes in prey resources.

Gradient compression garments protect against orthostatic intolerance during recovery from bed rest - Michael B. Stenger; Stuart M. C. Lee; L. Christine Ribeiro; Tiffany R. Phillips; Robert J. Ploutz-Snyder; Michael C. Willig; Christian M. Westby; Steven H. Platts (European Journal of Applied Physiology, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Development and characterization of 18 microsatellite loci for the spotted salamander (Ambystoma maculatum) using paired-end Illumina shotgun sequencing - William E. Peterman; Emily R. Brocato; Luke R. Pauley; Elsa C. Stuart; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Development and characterization of 22 microsatellite loci for the ringed salamander (Ambystoma annulatum) using paired-end Illumina shotgun sequencing - William E. Peterman; Luke R. Pauley; Emily R. Brocato; Elsa C. Stuart; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Evaluation of the Oxoid Brilliance™ CRE Agar for the detection of carbapenemase-producing Enterobacteriaceae - J. Cohen Stuart; G. Voets; W. Rottier; S. Voskuil; J. Scharringa; K. Dijk; A. C. Fluit; M. Leverstein-Van Hall (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

The nitrate time bomb: a numerical way to investigate nitrate storage and lag time in the unsaturated zone - L. Wang; A. S. Butcher; M. E. Stuart; D. C. Gooddy; J. P. Bloomfield (Environmental Geochemistry and Health, 2013)

Corrigendum to Cameron et al . 2013 - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)

Large birth size does not reduce negative latent effects of harsh environments across life stages in two coral species - Aaron C. Hartmann; Kristen L. Marhaver; Valérie F. Chamberland; Stuart A. Sandin; Mark J. A. Vermeij (Ecology, 2013)
When juveniles must tolerate harsh environments early in life, the disproportionate success of certain phenotypes across multiple early life stages will dramatically influence adult community composition and dynamics. In many species, large offspring have a higher tolerance for stressful environments than do smaller conspecifics (parental effects). However, we have a poor understanding of whether the benefits of increased parental investment carry over after juveniles escape harsh environments or progress to later life stages (latent effects). To investigate whether parental effects and latent effects interactively influence offspring success, we determined the degree to which latent effects of harsh abiotic conditions are mediated by offspring size in two stony coral species. Larvae of both species were sorted by size class and exposed to relatively high‐temperature or low‐salinity conditions. Survivorship was quantified for six days in these stressful environments, after which surviving larvae were placed in ambient conditions and evaluated for their ability to settle and metamorphose. We subsequently assessed long‐term post‐settlement survival of one species in its natural environment. Following existing theory, we expected that, within and between species, larger offspring would have a higher tolerance for harsh environmental conditions than smaller offspring. We found that large size did enhance offspring performance in each species. However, large offspring size within a species did not reduce the proportional, negative latent effects of harsh larval environments. Furthermore, the coral species that produces larger offspring was more, not less, prone to negative latent effects. We conclude that, within species, large offspring size does not increase resistance to latent effects. Comparing between species, we conclude that larger offspring size does not inherently confer greater robustness, and we instead propose that other life history characteristics such as larval duration better predict the tolerance of offspring to harsh and variable abiotic conditions. Additionally, when considering how stressful environments influence offspring performance, studies that only evaluate direct effects may miss crucial downstream (latent) effects on juveniles that have significant consequences for long‐term population dynamics.

Differences in the antibiotic susceptibility of human Escherichia coli with poultry-associated and non-poultry-associated extended-spectrum beta-lactamases - T. N. Platteel; M. A. Leverstein-Van Hall; J. W. Cohen Stuart; G. M. Voets; M. P. Munckhof; J. Scharringa; N. Sande; A. C. Fluit; M. J. M. Bonten (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Eco‐evolutionary dynamics in response to selection on life‐history - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)
Understanding the consequences of environmental change on ecological and evolutionary dynamics is inherently problematic because of the complex interplay between them. Using invertebrates in microcosms, we characterise phenotypic, population and evolutionary dynamics before, during and after exposure to a novel environment and harvesting over 20 generations. We demonstrate an evolved change in life‐history traits (the age‐ and size‐at‐maturity, and survival to maturity) in response to selection caused by environmental change (wild to laboratory) and to harvesting (juvenile or adult). Life‐history evolution, which drives changes in population growth rate and thus population dynamics, includes an increase in age‐to‐maturity of 76% (from 12.5 to 22 days) in the unharvested populations as they adapt to the new environment. Evolutionary responses to harvesting are outweighed by the response to environmental change (~ 1.4 vs. 4% change in age‐at‐maturity per generation). The adaptive response to environmental change converts a negative population growth trajectory into a positive one: an example of evolutionary rescue.

Permeability of Wellbore-Cement Fractures Following Degradation by Carbonated Brine - Stuart D. C. Walsh; Wyatt L. Du Frane; Harris E. Mason; Susan A. Carroll (Rock Mechanics and Rock Engineering, 2013)

HVP10 encoding V-PPase is a prime candidate for the barley HvNax3 sodium exclusion gene: evidence from fine mapping and expression analysis - Yuri Shavrukov; Jessica Bovill; Irfan Afzal; Julie E. Hayes; Stuart J. Roy; Mark Tester; Nicholas C. Collins (Planta, 2013)

A regional response in mean westerly circulation and rainfall to projected climate warming over Tasmania, Australia - Michael R. Grose; Stuart P. Corney; Jack J. Katzfey; James C. Bennett; Gregory K. Holz; Christopher J. White; Nathaniel L. Bindoff (Climate Dynamics, 2013)

Geographic evidence for source–sink dynamics in deep‐sea neogastropods of the eastern N orth A tlantic: an approach using nested analysis - Solange Brault; Carol T. Stuart; Martine C. Wagstaff; Michael A. Rex (Global Ecology and Biogeography, 2013)
Aim We conduct a nested analysis of bathymetric distributions in neogastropods to test the hypothesis that bathyal and abyssal populations represent a source–sink system. Abyssal assemblages are predicted to be significantly nested subsets of bathyal assemblages, and to be characterized by low density, which drives extinction, and a high incidence of species with larval dispersal for continued immigration to maintain diversity. Location Bathyal and abyssal regions of the eastern N orth A tlantic O cean. Methods We used published indices of beta diversity to distinguish the components of species dissimilarity among sites that are caused by turnover and nestedness. We used BINMATNEST and its most conservative null model to test specifically for nestedness along a depth gradient. Results Both turnover and nestedness affect beta diversity, but dissimilarity due to turnover predominates at depths of less than 3000 m, and dissimilarity due to nestedness at depths greater than 3000 m. Nestedness increases significantly down‐slope at depths greater than 1000 m. The rank order of nestedness is significantly predicted by macrofaunal density and by the proportion of neogastropod species with dispersing larvae. Main conclusions Bathymetric patterns of beta diversity in the deep‐sea benthos have been interpreted largely as a consequence of species turnover. Our results indicate that beta diversity in neogastropods is composed of two separate processes, turnover and nestedness, and that their relative importance changes with depth. Dissimilarity among sites due to nestedness, coupled with information on standing stock and life history, suggests that at least part of the abyssal neogastropod assemblage is maintained by source–sink dynamics.

Betaine supplementation enhances anabolic endocrine and Akt signaling in response to acute bouts of exercise - Jenna M. Apicella; Elaine C. Lee; Brooke L. Bailey; Catherine Saenz; Jeffrey M. Anderson; Stuart A. S. Craig; William J. Kraemer; Jeff S. Volek; Carl M. Maresh (European Journal of Applied Physiology, 2013)

Prescription drug dispensing profiles for one million children: a population-based analysis - Tingting Zhang; M. Anne Smith; Pat G. Camp; Salomah Shajari; Stuart M. MacLeod; Bruce C. Carleton (European Journal of Clinical Pharmacology, 2013)

The origin of Ag–Au–S–Se minerals in adularia-sericite epithermal deposits: constraints from the Broken Hills deposit, Hauraki Goldfield, New Zealand - Helen A. Cocker; Jeffrey L. Mauk; Stuart D. C. Rabone (Mineralium Deposita, 2013)

Observations of Surface Energy Fluxes and Boundary-Layer Structure Over Heron Reef, Great Barrier Reef, Australia - Mellissa C. MacKellar; Hamish A. McGowan; Stuart R. Phinn; Joshua S. Soderholm (Boundary-Layer Meteorology, 2013)

Persistent effects of chronic clozapine on the cellular and behavioral responses to LSD in mice - José L. Moreno; Terrell Holloway; Adrienne Umali; Vinayak Rayannavar; Stuart C. Sealfon; Javier González-Maeso (Psychopharmacology, 2013)

Protective Effects of 7,8-Dihydroxyflavone on Retinal Ganglion and RGC-5 Cells Against Excitotoxic and Oxidative Stress - Vivek K. Gupta; Yuyi You; Jonathan C. Li; Alexander Klistorner; Stuart L. Graham (Journal of Molecular Neuroscience, 2013)

Cardiac magnetic resonance imaging of rapid VCAM-1 up-regulation in myocardial ischemia–reperfusion injury - Stuart M. Grieve; Jacob Lønborg; Jawad Mazhar; Timothy C. Tan; Edwin Ho; Chia-Chi Liu; William Lay; Anthony J. Gill; Philip Kuchel; Ravinay Bhindi; Gemma A. Figtree (European Biophysics Journal, 2013)

Computational approaches to understanding dendritic cell responses to influenza virus infection - Elena Zaslavsky; Fernand Hayot; Stuart C. Sealfon (Immunologic Research, 2012)

Centralized mouse repositories - Leah Rae Donahue; Martin Hrabe de Angelis; Michael Hagn; Craig Franklin; K. C. Kent Lloyd; Terry Magnuson; Colin McKerlie; Naomi Nakagata; Yuichi Obata; Stuart Read; Wolfgang Wurst; Andreas Hörlein; et al. (Mammalian Genome, 2012)

The origin of litter chemical complexity during decomposition - Kyle Wickings; A. Stuart Grandy; Sasha C. Reed; Cory C. Cleveland (Ecology Letters, 2012)
The chemical complexity of decomposing plant litter is a central feature shaping the terrestrial carbon ( C ) cycle, but explanations of the origin of this complexity remain contentious. Here, we ask: How does litter chemistry change during decomposition, and what roles do decomposers play in these changes? During a long‐term (730 days) litter decomposition experiment, we tracked concurrent changes in decomposer community structure and function and litter chemistry using high‐resolution molecular techniques. Contrary to the current paradigm, we found that the chemistry of different litter types diverged, rather than converged, during decomposition due to the activities of decomposers. Furthermore, the same litter type exposed to different decomposer communities exhibited striking differences in chemistry, even after > 90% mass loss. Our results show that during decomposition, decomposer community characteristics regulate changes in litter chemistry, which could influence the functionality of litter‐derived soil organic matter ( SOM ) and the turnover and stabilisation of soil C.

Eruption of kimberlite magmas: physical volcanology, geomorphology and age of the youngest kimberlitic volcanoes known on earth (the Upper Pleistocene/Holocene Igwisi Hills volcanoes, Tanzania) - Richard J. Brown; S. Manya; I. Buisman; G. Fontana; M. Field; C. Mac Niocaill; R. S. J. Sparks; F. M. Stuart (Bulletin of Volcanology, 2012)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

Experimental litterfall manipulation drives large and rapid changes in soil carbon cycling in a wet tropical forest - Jonathan W. Leff; William R. Wieder; Philip G. Taylor; Alan R. Townsend; Diana R. Nemergut; A. Stuart Grandy; Cory C. Cleveland (Global Change Biology, 2012)
Global changes such as variations in plant net primary production are likely to drive shifts in leaf litterfall inputs to forest soils, but the effects of such changes on soil carbon ( C ) cycling and storage remain largely unknown, especially in C ‐rich tropical forest ecosystems. We initiated a leaf litterfall manipulation experiment in a tropical rain forest in C osta R ica to test the sensitivity of surface soil C pools and fluxes to different litter inputs. After only 2 years of treatment, doubling litterfall inputs increased surface soil C concentrations by 31%, removing litter from the forest floor drove a 26% reduction over the same time period, and these changes in soil C concentrations were associated with variations in dissolved organic matter fluxes, fine root biomass, microbial biomass, soil moisture, and nutrient fluxes. However, the litter manipulations had only small effects on soil organic C ( SOC ) chemistry, suggesting that changes in C cycling, nutrient cycling, and microbial processes in response to litter manipulation reflect shifts in the quantity rather than quality of SOC . The manipulation also affected soil CO 2 fluxes; the relative decline in CO 2 production was greater in the litter removal plots (−22%) than the increase in the litter addition plots (+15%). Our analysis showed that variations in CO 2 fluxes were strongly correlated with microbial biomass pools, soil C and nitrogen ( N ) pools, soil inorganic P fluxes, dissolved organic C fluxes, and fine root biomass. Together, our data suggest that shifts in leaf litter inputs in response to localized human disturbances and global environmental change could have rapid and important consequences for belowground C storage and fluxes in tropical rain forests, and highlight differences between tropical and temperate ecosystems, where belowground C cycling responses to changes in litterfall are generally slower and more subtle.

Roots and fungi accelerate carbon and nitrogen cycling in forests exposed to elevated CO 2 - Richard P. Phillips; Ina C. Meier; Emily S. Bernhardt; A. Stuart Grandy; Kyle Wickings; Adrien C. Finzi (Ecology Letters, 2012)
A common finding in multiple CO 2 enrichment experiments in forests is the lack of soil carbon ( C ) accumulation owing to microbial priming of ‘old’ soil organic matter ( SOM ). However, soil C losses may also result from the accelerated turnover of ‘young’ microbial tissues that are rich in nitrogen ( N ) relative to bulk SOM . We measured root‐induced changes in soil C dynamics in a pine forest exposed to elevated CO 2 and N enrichment by combining stable isotope analyses, molecular characterisations of SOM and microbial assays. We find strong evidence that the accelerated turnover of root‐derived C under elevated CO 2 is sufficient in magnitude to offset increased belowground inputs. In addition, the C losses were associated with accelerated N cycling, suggesting that trees exposed to elevated CO 2 not only enhance N availability by stimulating microbial decomposition of SOM via priming but also increase the rate at which N cycles through microbial pools.

An in vitro mutagenesis protocol for the production of sugarcane tolerant to the herbicide imazapyr - Aimée C. Koch; Sumita Ramgareeb; R. Stuart Rutherford; Sandra J. Snyman; M. Paula Watt (In Vitro Cellular & Developmental Biology - Plant, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Erratum to: Activity of cortical and thalamic neurons during the slow (<1 Hz) rhythm in the mouse in vivo - Vincenzo Crunelli; Magor L. Lőrincz; Ying Bao; Adam C. Errington; Stuart W. Hughes (Pflügers Archiv - European Journal of Physiology, 2012)

The Effects of Soil Bacterial Community Structure on Decomposition in a Tropical Rain Forest - Jonathan W. Leff; Diana R. Nemergut; A. Stuart Grandy; Sean P. O’Neill; Kyle Wickings; Alan R. Townsend; Cory C. Cleveland (Ecosystems, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Population vulnerability to climate change linked to timing of breeding in boreal ducks - Mark C. Drever; Robert G. Clark; Chris Derksen; Stuart M. Slattery; Peter Toose; Thomas D. Nudds (Global Change Biology, 2012)
Identifying and understanding why traits make species vulnerable to changing climatic conditions remain central problems in evolutionary and applied ecology. We used spring snow cover duration as a proxy for phenological timing of wetland ecosystems, and examined how snow cover duration during spring and during the entire snow season affected population dynamics of duck species breeding in the western boreal forest of N orth A merica, 1973–2007. We predicted that population level responses would differ among duck species, such that late‐nesting species with reduced flexibility in their timing of breeding, i.e. scaup ( A ythya spp.) and scoter ( M elanitta spp.), would be more strongly affected by changing snow cover conditions relative to species better able to adjust timing of breeding to seasonal phenology, i.e. mallard ( A nas platyrhynchos ) and A merican wigeon ( A nas americana ). Population growth rates of scaup and scoter were positively linked to spring snow cover duration; after accounting for effects of density dependence, larger populations resulted after springs with long snow cover duration than after springs with short snow cover duration. In contrast, population growth rates of mallard and wigeon were either negatively or only weakly associated with snow cover duration. Duck population models were then incorporated with snow cover duration derived from climate model simulations under the A2 emission scenario, and these predictions suggested that late‐nesting duck species will experience the most severe population declines. Results are consistent with a hypothesis that the gradual climatic warming observed in the western boreal forest of N orth A merica has contributed to and may continue to exacerbate population declines of scaup and scoter.

Activity of cortical and thalamic neurons during the slow (<1 Hz) rhythm in the mouse in vivo - Vincenzo Crunelli; Magor L. Lőrincz; Adam C. Errington; Stuart W. Hughes (Pflügers Archiv - European Journal of Physiology, 2012)

Terrestrial invertebrates of dry river beds are not simply subsets of riparian assemblages - Alisha L. Steward; Jonathan C. Marshall; Fran Sheldon; Bronwyn Harch; Satish Choy; Stuart E. Bunn; Klement Tockner (Aquatic Sciences, 2011)

Biomarkers of Fruit and Vegetable Intake in Human Intervention Studies: A Systematic Review - Francina R. Baldrick; Jayne V. Woodside; J. Stuart Elborn; Ian S. Young; Michelle C. McKinley (Critical Reviews in Food Science and Nutrition, 2011)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

Seasonal occurrence and distribution of Bryde's whales in the Hauraki Gulf, New Zealand - Nicky Wiseman; Stuart Parsons; Karen A. Stockin; C. Scott Baker (Marine Mammal Science, 2011)
The Hauraki Gulf is a large, shallow embayment located north of Auckland City (36°51′S, 174°46′E), New Zealand. Bryde's whales ( Balaenoptera edeni) are the most frequently observed balaenopterid in these waters. To assess the use of the Hauraki Gulf for this species, we examined the occurrence and distribution in relation to environmental parameters. Data were collected from a platform of opportunity during 674 daily surveys between March 2003 and February 2006. A total of 760 observations of Bryde's whales were recorded throughout the study period during 371 surveys. The number of Bryde's whales sighted/day was highest in winter, coinciding with the coolest median sea‐surface temperature (14.6°C). Bryde's whales were recorded throughout the Hauraki Gulf in water depths ranging from 12.1–59.8 m (mean = 42.3, SD = 5.1). Cow–calf pairs were most frequently observed during the austral autumn in water depths of 29.9–53.9 m (mean = 40.8, SD = 5.2). Data from this study suggest Bryde's whales in the Hauraki Gulf exhibit a mix of both “inshore” and “offshore” characteristics from the Bryde's whales examined off the coast of South Africa.

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Near infrared spectroscopy-derived interstitial hydrogen ion concentration and tissue oxygen saturation during ambulation - Stuart M. C. Lee; Mark S. F. Clarke; Daniel P. O’Connor; Leah Stroud; Gwenn E. C. Ellerby; Babs R. Soller (European Journal of Applied Physiology, 2011)

A Method for Ensemble Wildland Fire Simulation - Mark A. Finney; Isaac C. Grenfell; Charles W. McHugh; Robert C. Seli; Diane Trethewey; Richard D. Stratton; Stuart Brittain (Environmental Modeling & Assessment, 2011)

Toward a Management Framework for Networks of Protected Areas in the Face of Climate Change - DAVID G. HOLE; BRIAN HUNTLEY; JULIUS ARINAITWE; STUART H. M. BUTCHART; YVONNE C. COLLINGHAM; LINCOLN D. C. FISHPOOL; DEBORAH J. PAIN; STEPHEN G. WILLIS (Conservation Biology, 2011)
Networks of sites of high importance for conservation of biological diversity are a cornerstone of current conservation strategies but are fixed in space and time. As climate change progresses, substantial shifts in species’ ranges may transform the ecological community that can be supported at a given site. Thus, some species in an existing network may not be protected in the future or may be protected only if they can move to sites that in future provide suitable conditions. We developed an approach to determine appropriate climate‐change adaptation strategies for individual sites within a network that was based on projections of future changes in the relative proportions of emigrants (species for which a site becomes climatically unsuitable), colonists (species for which a site becomes climatically suitable), and persistent species (species able to remain within a site despite the climatic change). Our approach also identifies key regions where additions to a network could enhance its future effectiveness. Using the sub‐Saharan African Important Bird Area (IBA) network as a case study, we found that appropriate conservation strategies for individual sites varied widely across sub‐Saharan Africa, and key regions where new sites could help increase network robustness varied in space and time. Although these results highlight the potential difficulties within any planning framework that seeks to address climate‐change adaptation needs, they demonstrate that such planning frameworks are necessary, if current conservation strategies are to be adapted effectively, and feasible, if applied judiciously.

NIR Spectroscopy Applications in the Development of a Compacted Multiparticulate System for Modified Release - Stuart L. Cantor; Stephen W. Hoag; Christopher D. Ellison; Mansoor A. Khan; Robbe C. Lyon (AAPS PharmSciTech, 2011)

Qualitative Variation in Proanthocyanidin Composition of Populus Species and Hybrids: Genetics is the Key - Ashley N. Scioneaux; Michael A. Schmidt; Melissa A. Moore; Richard L. Lindroth; Stuart C. Wooley; Ann E. Hagerman (Journal of Chemical Ecology, 2011)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)

Synthesizing mechanisms of density dependence in reef fishes: behavior, habitat configuration, and observational scale - J. Wilson White; Jameal F. Samhouri; Adrian C. Stier; Clare L. Wormald; Scott L. Hamilton; Stuart A. Sandin (Ecology, 2010)
Coral and rocky reef fish populations are widely used as model systems for the experimental exploration of density‐dependent vital rates, but patterns of density‐dependent mortality in these systems are not yet fully understood. In particular, the paradigm for strong, directly density‐dependent (DDD) postsettlement mortality stands in contrast to recent evidence for inversely density‐dependent (IDD) mortality. We review the processes responsible for DDD and IDD per capita mortality in reef fishes, noting that the pattern observed depends on predator and prey behavior, the spatial configuration of the reef habitat, and the spatial and temporal scales of observation. Specifically, predators tend to produce DDD prey mortality at their characteristic spatial scale of foraging, but prey mortality is IDD at smaller spatial scales due to attack‐abatement effects (e.g., risk dilution). As a result, DDD mortality may be more common than IDD mortality on patch reefs, which tend to constrain predator foraging to the same scale as prey aggregation, eliminating attack‐abatement effects. Additionally, adjacent groups of prey on continuous reefs may share a subset of refuges, increasing per capita refuge availability and relaxing DDD mortality relative to prey on patch reefs, where the patch edge could prevent such refuge sharing. These hypotheses lead to a synthetic framework to predict expected mortality patterns for a variety of scenarios. For nonsocial, nonaggregating species and species that aggregate in order to take advantage of spatially clumped refuges, IDD mortality is possible but likely superseded by DDD refuge competition, especially on patch reefs. By contrast, for species that aggregate socially, mortality should be IDD at the scale of individual aggregations but DDD at larger scales. The results of nearly all prior reef fish studies fit within this framework, although additional work is needed to test many of the predicted outcomes. This synthesis reconciles some apparent contradictions in the recent reef fish literature and suggests the importance of accounting for the scale‐sensitive details of predator and prey behavior in any study system.

A model of direction selectivity in the starburst amacrine cell network - Germán A. Enciso; Michael Rempe; Andrey V. Dmitriev; Konstantin E. Gavrikov; David Terman; Stuart C. Mangel (Journal of Computational Neuroscience, 2010)

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Patterns of Citations of Open Access and Non‐Open Access Conservation Biology Journal Papers and Book Chapters - MICHAEL C. CALVER; J. STUART BRADLEY (Conservation Biology, 2010)
Open access (OA) publishing, whereby authors, their institutions, or their granting bodies pay or provide a repository through which peer‐reviewed work is available online for free, is championed as a model to increase the number of citations per paper and disseminate results widely, especially to researchers in developing countries. We compared the number of citations of OA and non‐OA papers in six journals and four books published since 2000 to test whether OA increases number of citations overall and increases citations made by authors in developing countries. After controlling for type of paper (e.g., review or research paper), length of paper, authors’ citation profiles, number of authors per paper, and whether the author or the publisher released the paper in OA, OA had no statistically significant influence on the overall number of citations per journal paper. Journal papers were cited more frequently if the authors had published highly cited papers previously, were members of large teams of authors, or published relatively long papers, but papers were not cited more frequently if they were published in an OA source. Nevertheless, author‐archived OA book chapters accrued up to eight times more citations than chapters in the same book that were not available through OA, perhaps because there is no online abstracting service for book chapters. There was also little evidence that journal papers or book chapters published in OA received more citations from authors in developing countries relative to those journal papers or book chapters not published in OA. For scholarly publications in conservation biology, only book chapters had an OA citation advantage, and OA did not increase the number of citations papers or chapters received from authors in developing countries .

Changes in fire regime break the legacy lock on successional trajectories in Alaskan boreal forest - JILL F. JOHNSTONE; TERESA N. HOLLINGSWORTH; F. STUART CHAPIN; MICHELLE C. MACK (Global Change Biology, 2010)
Predicting plant community responses to changing environmental conditions is a key element of forecasting and mitigating the effects of global change. Disturbance can play an important role in these dynamics, by initiating cycles of secondary succession and generating opportunities for communities of long‐lived organisms to reorganize in alternative configurations. This study used landscape‐scale variations in environmental conditions, stand structure, and disturbance from an extreme fire year in Alaska to examine how these factors affected successional trajectories in boreal forests dominated by black spruce. Because fire intervals in interior Alaska are typically too short to allow relay succession, the initial cohorts of seedlings that recruit after fire largely determine future canopy composition. Consequently, in a dynamically stable landscape, postfire tree seedling composition should resemble that of the prefire forest stands, with little net change in tree composition after fire. Seedling recruitment data from 90 burned stands indicated that postfire establishment of black spruce was strongly linked to environmental conditions and was highest at sites that were moist and had high densities of prefire spruce. Although deciduous broadleaf trees were absent from most prefire stands, deciduous trees recruited from seed at many sites and were most abundant at sites where the fires burned severely, consuming much of the surface organic layer. Comparison of pre‐ and postfire tree composition in the burned stands indicated that the expected trajectory of black spruce self‐replacement was typical only at moist sites that burned with low fire severity. At severely burned sites, deciduous trees dominated the postfire tree seedling community, suggesting these sites will follow alternative, deciduous‐dominated trajectories of succession. Increases in the severity of boreal fires with climate warming may catalyze shifts to an increasingly deciduous‐dominated landscape, substantially altering landscape dynamics and ecosystem services in this part of the boreal forest.

Informed consent to tissue donation: policies and practice - Andrew Siegel; Martha W. Anderson; Tracy C. Schmidt; Stuart J. Youngner (Cell and Tissue Banking, 2009)

Evaluation of the genetic variability of orchid fleck virus by single-strand conformational polymorphism analysis and nucleotide sequencing of a fragment from the nucleocapsid gene - Karen Sumire Kubo; R. M. Stuart; J. Freitas-Astúa; R. Antonioli-Luizon; E. C. Locali-Fabris; H. D. Coletta-Filho; M. A. Machado; E. W. Kitajima (Archives of Virology, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Projected impacts of climate change on a continent‐wide protected area network - David G. Hole; Stephen G. Willis; Deborah J. Pain; Lincoln D. Fishpool; Stuart H. M. Butchart; Yvonne C. Collingham; Carsten Rahbek; Brian Huntley (Ecology Letters, 2009)
Despite widespread concern, the continuing effectiveness of networks of protected areas under projected 21st century climate change is uncertain. Shifts in species’ distributions could mean these resources will cease to afford protection to those species for which they were originally established. Using modelled projected shifts in the distributions of sub‐Saharan Africa’s entire breeding avifauna, we show that species turnover across the continent’s Important Bird Area (IBA) network is likely to vary regionally and will be substantial at many sites (> 50% at 42% of IBAs by 2085 for priority species). Persistence of suitable climate space across the network as a whole, however, is notably high, with 88–92% of priority species retaining suitable climate space in ≥ 1 IBA(s) in which they are currently found. Only 7–8 priority species lose climatic representation from the network. Hence, despite the likelihood of significant community disruption, we demonstrate that rigorously defined networks of protected areas can play a key role in mitigating the worst impacts of climate change on biodiversity.

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Early Life Stress on Brain Structure and Function Across the Lifespan: A Preliminary Study - Donna L. Seckfort; Robert Paul; Stuart M. Grieve; Brian Vandenberg; Richard A. Bryant; Leanne M. Williams; C. Richard Clark; Ronald A. Cohen; Steven Bruce; Evian Gordon (Brain Imaging and Behavior, 2008)

Antimicrobial Peptides and their Potential as Oral Therapeutic Agents - Stuart G. Dashper; Sze Wei Liu; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Gene Expression of Different Wheat Genotypes During Attack by Virulent and Avirulent Hessian Fly (Mayetiola destructor) Larvae - Xuming Liu; Jianfa Bai; Li Huang; Lieceng Zhu; Xiang Liu; Nanyan Weng; John C. Reese; Marion Harris; Jeffrey J. Stuart; Ming-Shun Chen (Journal of Chemical Ecology, 2007)

Introgressed and endogenous Mi-1 gene clusters in tomato differ by complex rearrangements in flanking sequences and show sequence exchange and diversifying selection among homologues - Stuart Seah; Adam C. Telleen; Valerie M. Williamson (Theoretical and Applied Genetics, 2007)

Putative ammonia‐oxidizing Crenarchaeota in suboxic waters of the Black Sea: a basin‐wide ecological study using 16S ribosomal and functional genes and membrane lipids - Marco J. L. Coolen; Ben Abbas; Judith Van Bleijswijk; Ellen C. Hopmans; Marcel M. M. Kuypers; Stuart G. Wakeham; Jaap S. Sinninghe Damsté (Environmental Microbiology, 2007)
Summary Within the upper 400 m at western, central and eastern stations in the world's largest stratified basin, the Black Sea, we studied the qualitative and quantitative distribution of putative nitrifying Archaea based on their genetic markers (16S rDNA, amoA encoding for the alpha‐subunit of archaeal ammonia monooxygenase), and crenarchaeol, the specific glycerol diphytanyl glycerol tetraether of pelagic Crenarchaeota within the Group I.1a. Marine Crenarchaeota were the most abundant Archaea (up to 98% of the total archaeal 16S rDNA copies) in the suboxic layers with oxygen levels as low as 1 μM including layers where previously anammox bacteria were described. Different marine crenarchaeotal phylotypes (both 16S rDNA and amoA ) were found at the upper part of the suboxic zone as compared with the base of the suboxic zone and the upper 15–30 m of the anoxic waters with prevailing sulfide concentrations of up to 30 μM. Crenarchaeol concentrations were higher in the sulfidic chemocline as compared with the suboxic zone. These results indicate an abundance of putative nitrifying Archaea at very low oxygen levels within the Black Sea and might form an important source of nitrite for the anammox reaction.

The presence of ladderane lipids in the oxygen minimum zone of the Arabian Sea indicates nitrogen loss through anammox - Andrea Jaeschke; Ellen C. Hopmans; Stuart G. Wakeham; Stefan Schouten; Jaap S. Sinninghe Damsté (Limnology and Oceanography, 2007)
Distributions of ladderane lipids, which are characteristic of membranes of bacteria performing anaerobic ammonium oxidation (anammox), were determined in the northwestern Arabian Sea with respect to season, depth, and distance to the coast of Oman. Ladderane lipids were detected and quantified in suspended particulate matter (SPM) obtained from various water depths along a northwest‐to‐southeast transect during the spring intermonsoon period. Maximum concentrations of 5‐8 pg L −1 generally occurred at 500 m in the upper part of the oxygen minimum zone (OMZ). Fluxes of ladderane lipids obtained from sediment trap material sampled at 500‐m water depth ~350 km off the coast reveal a strong seasonal pattern apparently related to the annual monsoon cycle in the northern Arabian Sea, with highest fluxes of 125 ng m −2 d −1 observed during the southwest monsoon. This fourfold increase in flux during the SW monsoon compared to the spring intermonsoon period may indicate higher anammox bacterial productivity or enhanced export of ladderanes during a period of high particulate matter flux or both. Anammox, in addition to denitrification, seems to be responsible for a significant loss of nutrient nitrogen from OMZ waters in the Arabian Sea.

Natural and anthropogenic changes to mangrove distributions in the Pioneer River Estuary (QLD, Australia) - Stacy D. Jupiter; Donald C. Potts; Stuart R. Phinn; Norman C. Duke (Wetlands Ecology and Management, 2007)

Influence of river inflows on plankton distribution around the southern perimeter of the Salton Sea, California - Kristen M. Reifel; Brandon K. Swan; Errel Olivo; James M. Watts; Charles C. Trees; Stuart H. Hurlbert (Hydrobiologia, 2007)

Historical reflections on the afterhyperpolarization–firing rate relation of vertebrate spinal neurons - E. K. Stauffer; J. C. McDonagh; T. G. Hornby; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2007)

Aerobic and anaerobic methanotrophs in the Black Sea water column - Carsten J. Schubert; Marco J. L. Coolen; Lev N. Neretin; Axel Schippers; Ben Abbas; Edith Durisch‐Kaiser; Bernhard Wehrli; Ellen C. Hopmans; Jaap S. Sinninghe Damsté; Stuart Wakeham; Marcel M. M. Kuypers (Environmental Microbiology, 2006)
Summary Inputs of CH 4 from sediments, including methane seeps on the continental margin and methane‐rich mud volcanoes on the abyssal plain, make the Black Sea the world’s largest surface water reservoir of dissolved methane and drive a high rate of aerobic and anaerobic oxidation of methane in the water column. Here we present the first combined organic geochemical and molecular ecology data on a water column profile of the western Black Sea. We show that aerobic methanotrophs type I are responsible for methane oxidation in the oxic water column and ANME‐1‐ and ANME‐2‐related organisms for anaerobic methane oxidation. The occurrence of methanotrophs type I cells in the anoxic zone suggests that inactive cells settle to deeper waters. Molecular and biomarker results suggest that a clear distinction between the occurrence of ANME‐1‐ and ANME‐2‐related lineages exists, i.e. ANME‐1‐related organisms are responsible for anaerobic methane oxidation below 600 m water depth, whereas ANME‐2‐related organisms are responsible for this process in the anoxic water column above approximately 600 m water depth.

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

The Contribution of Crab Burrow Excavation to Carbon Availability in Surficial Salt-marsh Sediments - Jorge L. Gutiérrez; Clive G. Jones; Peter M. Groffman; Stuart E. G. Findlay; Oscar O. Iribarne; Pablo D. Ribeiro; C. Martín Bruschetti (Ecosystems, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Accumulation of Knowledge and Changes in Red List Classifications within the Family Galliformes1980–2004 - David C. Lee; Stuart J. Marsden (Biodiversity and Conservation, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

A protocol for high-throughput phenotyping, suitable for quantitative trait analysis in mice - Leah C. Solberg; William Valdar; Dominique Gauguier; Graciela Nunez; Amy Taylor; Stephanie Burnett; Carmen Arboledas-Hita; Polinka Hernandez-Pliego; Stuart Davidson; Peter Burns; Shoumo Bhattacharya; Tertius Hough; et al. (Mammalian Genome, 2006)

Multi-Scale Controls on Water Quality Effects of Submerged Aquatic Vegetation in the Tidal Freshwater Hudson River - Stuart E. G. Findlay; William C. Nieder; Elizabeth A. Blair; David T. Fischer (Ecosystems, 2006)

Importance of species interactions to community heritability: a genetic basis to trophic‐level interactions - Joseph K. Bailey; Stuart C. Wooley; Richard L. Lindroth; Thomas G. Whitham (Ecology Letters, 2006)
Recent community genetics studies have shown that specific genotypes of a host plant support distinct arthropod communities. Building upon these findings, we examined the hypothesis that a trophic community consisting of cottonwood trees, a galling herbivore and avian predators could also be related to the genetics of the host tree. We found genetic correlations among phytochemistry of individual tree genotypes, the density of a galling herbivore, and the intensity of avian predation on these herbivores. We detected significant broad‐sense heritability of these interactions that range from H = 0.70 to 0.83. The genetic basis of these interactions tended to increase across trophic levels suggesting that small genetic changes in the cottonwood phenotype could have major consequences at higher trophic levels affecting species interactions and energy flow. These findings show a heritable basis to trophic‐level interactions indicating that there is a significant genetic basis to community composition and energy flow that is predictable by plant genotype. Our data clearly link plant genetics to patterns of avian foraging and show that species interactions are important components of community heritability and ecosystem processes. Overall, these data support the hypothesis that evolution of plant traits can alter trophic‐level interactions and community composition.

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Mixtures of UK Wheat as an Efficient and Environmentally Friendly Source for Bioethanol - J. Stuart Swanston; Adrian C. Newton (Journal of Industrial Ecology, 2005)
Summary Concerns about access to oil supplies have encouraged the exploration of renewable fuel and energy sources. Industrial ecology offers tools to compare the energy implications and benefits of differing strategies, but using botanical sources of raw materials to replace nonrenewable ones also requires appreciation of plant science, especially the variation in genetic potential within species. Whereas cultivation methods determine whether genetic potential is realized, different methods impact the environment to varying degrees. Experience with barley variety mixtures, aimed at reducing chemical input, has shown them to improve yield and reduce disease, while maintaining or even enhancing quality. Yield improvements still occurred in the absence of disease and increased in proportion to the number of component varieties. Because other research showed mixtures to be similarly effective in wheat, a protocol to grow and exploit a complex mixture of soft wheat is proposed, offering a cost‐effective and energy efficient feedstock for a possible bioethanol industry in the United Kingdom. Ethanol would be produced initially from grain, with the straw used for heating or electricity generation. Fertilizer production and use and vehicle fuels have been shown as the main forms of energy consumption in growing a crop, and targets for enhancing the energy balance, by growing mixtures under an integrated farming system, are postulated. A close but negative association between grain protein and alcohol yield is demonstrated and a mixture giving comparable grain yield, but superior alcohol yield, to its best component is identified. Mixing varieties differing in plant morphology may also increase total biomass yield and, therefore, the energy generated from the crop. Pesticide reduction has another positive, though small, effect on the energy balance, from using mixtures. Eliminating prophylactic spraying also reduces vehicle fuel consumption, and may provide the low‐toxicity benefits of organic agriculture without the yield penalty. A range of alternative uses for straw and other by‐products is also discussed.

Measurement and nature of firing rate adaptation in turtle spinal neurons - R. B. Gorman; J. C. McDonagh; T. G. Hornby; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2005)

The Brachyspira hyodysenteriae ftnA Gene: DNA Vaccinationand Real-Time PCR Quantification of Bacteria in a Mouse Modelof Disease - Antony J. Davis; Stuart C. Smith; Robert J. Moore (Current Microbiology, 2005)

Persistence of aquatic refugia between flow pulses in a dryland river system(Cooper Creek, Australia) - Stephen K. Hamilton; Stuart E. Bunn; Martin C. Thoms; Jonathan C. Marshall (Limnology and Oceanography, 2005)
In many dryland rivers with intermittent flow, relatively deep segments of the river channel serve as refugia for aquatic life during protracted intervals between flows. Semipermanent channel segments are known as waterholes in the semiarid Cooper Creek system of western Queensland. Fractional water loss by evaporation was estimated in 15 Cooper waterholes from the increase in conservative ion (Na + and Cl − ) concentrations and independently from evaporative fractionation of oxygen and hydrogen isotopes in water. The major solute chemistry and isotope results indicated that evaporative water loss controlled the water levels between flows and that the surface waters were effectively isolated from underlying groundwater that had a distinctive chemical and isotopic composition. Fractional water loss rates combined with stage‐volume relationships for each basin showed a mean evaporative loss rate of 2.1 m yr −1 ; during that time (April‐October 2002), pan evaporation averaged 2.5 m yr −1 . Site‐specific extrapolation of those estimated evaporative loss rates indicated that the waterholes would dry to 10% of their bankfull volumes in 6‐23 months, although those estimates were based on sampling in 2002, when pan evaporation rates were 18% higher than the long‐term mean. These persistence times show the importance of occasional, irregular flow pulses in sustaining these aquatic refugia; the desiccation of waterholes could become more common if future water withdrawals reduce the frequency and intensity of river flows to the point where they occur less often than annually.

Postfire Soil N Cycling in Northern Conifer Forests Affected by Severe, Stand-Replacing Wildfires - Erica A. H. Smithwick; Monica G. Turner; Michelle C. Mack; F. Stuart Chapin (Ecosystems, 2005)

Influence of Tree Species on Forest Nitrogen Retention in the Catskill Mountains, New York, USA - Pamela H. Templer; Gary M. Lovett; Kathleen C. Weathers; Stuart E. Findlay; Todd E. Dawson (Ecosystems, 2005)

Afterhyperpolarization?firing rate relation of turtle spinal neurons - E. K. Stauffer; D. G. Stuart; J. C. McDonagh; T. G. Hornby; R. M. Reinking (Journal of Comparative Physiology A, 2005)

Three-dimensional Structure of an Old-growth Pseudotsuga-Tsuga Canopy and Its Implications for Radiation Balance, Microclimate, and Gas Exchange - Geoffrey G. Parker; Mark E. Harmon; Michael A. Lefsky; Jiquan Chen; Robert Van Pelt; Stuart B. Weis; Sean C. Thomas; William E. Winner; David C. Shaw; Jerry F. Frankling (Ecosystems, 2004)

Cell Surface Display of the Chlamydial Glycolipid Exoantigen (GLXA) Demonstrated by Antibody-Dependent Complement-Mediated Cytotoxicity - Wilmore C. Webley; Gary J. Vora; Elizabeth S. Stuart (Current Microbiology, 2004)

Resistance to disuse atrophy in a turtle hindlimb muscle - J. C. McDonagh; R. J. Callister; M. L. Favron; D. G. Stuart (Journal of Comparative Physiology A, 2004)

Assessing the diet of great skuas, Catharacta skua, using five different techniques - Stephen C. Votier; Stuart Bearhop; Aidan MacCormick; Norman Ratcliffe; Robert W. Furness (Polar Biology, 2003)

Legitimizing Fluvial Ecosystems as Users of Water: An Overview - ROBERT J. NAIMAN; STUART E. BUNN; CHRISTER NILSSON; GEOFF E. PETTS; GILLES PINAY; LISA C. THOMPSON (Environmental Management, 2002)

The use of sectioned otoliths to age barramundi (Lates calcarifer) (Bloch, 1790) [Centropomidae] - Ivor G. Stuart; Stephen C. McKillup (Hydrobiologia, 2002)

Catchment-Scale Variation in the Nitrate Concentrations of Groundwater Seeps in the Catskill Mountains, New York, U.S.A. - A. Joshua West; Stuart E. G. Findlay; Douglas A. Burns; Kathleen C. Weathers; Gary M. Lovett (Water, Air, & Soil Pollution, 2001)

Pleurochrysis pseudoroscoffensis (Prymnesiophyceae) blooms on the surface of the Salton Sea, California - Kristen M. Reifel; Michael P. McCoy; Mary Ann Tiffany; Tonie E. Rocke; Charles C. Trees; Steven B. Barlow; D. John Faulkner; Stuart H. Hurlbert (Hydrobiologia, 2001)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

The Leishmania genome project: new insights into gene organization and function - Peter J. Myler; Stephen M. Beverley; Angela K. Cruz; Deborah E. Dobson; Alasdair C. Ivens; Paul D. McDonagh; Rentala Madhubala; Santiago Martinez-Calvillo; Jeronimo C. Ruiz; Alka Saxena; Ellen Sisk; Susan M. Sunkin; et al. (Medical Microbiology and Immunology, 2001)

Genomic structure, expression, and chromosome mapping of the mouse homologue for the WSL-1 ( DR3 , Apo3 , TRAMP , LARD , TR3 , TNFRSF12 ) gene - Eddie C. Y. Wang; Jeremy Kitson; Anette Thern; Jill Williamson; Stuart N. Farrow; Michael J. Owen (Immunogenetics, 2001)

Geographic patterns and dynamics of Alaskan climate interpolated from a sparse station record - Michael D. Fleming; F. Stuart Chapin; Wolfgang Cramer; Gary L. Hufford; Mark C. Serreze (Global Change Biology, 2000)
Summary Data from a sparse network of climate stations in Alaska were interpolated to provide 1‐km resolution maps of mean monthly temperature and precipitation–‐variables that are required at high spatial resolution for input into regional models of ecological processes and resource management. The interpolation model is based on thin‐plate smoothing splines, which uses the spatial data along with a digital elevation model to incorporate local topography. The model provides maps that are consistent with regional climatology and with patterns recognized by experienced weather forecasters. The broad patterns of Alaskan climate are well represented and include latitudinal and altitudinal trends in temperature and precipitation and gradients in continentality. Variations within these broad patterns reflect both the weakening and reduction in frequency of low‐pressure centres in their eastward movement across southern Alaska during the summer, and the shift of the storm tracks into central and northern Alaska in late summer. Not surprisingly, apparent artifacts of the interpolated climate occur primarily in regions with few or no stations. The interpolation model did not accurately represent low‐level winter temperature inversions that occur within large valleys and basins. Along with well‐recognized climate patterns, the model captures local topographic effects that would not be depicted using standard interpolation techniques. This suggests that similar procedures could be used to generate high‐ resolution maps for other high‐latitude regions with a sparse density of data.

Modulation of corneal endothelial hydration control mechanisms by Rolipram - Christopher G. Wigham; Helen C. Turner; Jeremy Swan; Stuart A. Hodson (Pflügers Archiv - European Journal of Physiology, 2000)

Cloning, sequencing and analysis of the pucC genes from Rubrivivax gelatinosus strain 151 and Rhodopseudomonas acidophila strain 10050 - Adrian E. Simmons; Stuart J. Barrett; C. Neil Hunter; Richard J.R. Cogdell (Photosynthesis Research, 2000)

Comparison of functional annotation schemes for genomes - Stuart C. G. Rison; T. Charles Hodgman; Janet M. Thornton (Functional & Integrative Genomics, 2000)

Comparison of functional annotation schemes for genomes - Stuart C. G. Rison; T. Charles Hodgman; Janet M. Thornton (Functional & Integrative Genomics, 2000)

Age constraints to the relationships between magmatism, metamorphism and tectonism in the Aracena metamorphic belt, southern Spain - A. Castro; C. Fernández; H. El-Hmidi; M. El-Biad; M. Díaz; J. de la Rosa; F. Stuart (International Journal of Earth Sciences, 1999)

Outbreak of Escherichia coli O157 Infection Associated with a Music Festival - T. Cheasty; J. Stuart; M. Crampin; G. Willshaw; T. Djuretic; R. Hancock; C. Elstob; A. Rouse (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Effects of seasonal growth rate on morphological variation of Undaria pinnatifida (Alariaceae, Phaeophyceae) - M. D. Stuart; C. L. Hurd; M. T. Brown (Hydrobiologia, 1999)

No Evidence for Kin Discrimination in Cannibalistic Tree-Hole Mosquitoes (Diptera: Culicidae) - Thomas N. Sherratt; Sarah E. Ruff; Stuart C. Church (Journal of Insect Behavior, 1999)

Local genetic structure in red grouse ( Lagopus lagopus scoticus ): evidence from microsatellite DNA markers - STUART B. PIERTNEY; ANDREW D. C. MACCOLL; PHILIP J. BACON; JOHN F. DALLAS (Molecular Ecology, 1998)
Allelic variation at seven hypervariable tri‐ and tetranucleotide microsatellite loci was used to determine levels of population differentiation between 14 populations of red grouse ( Lagopus lagopus scoticus ) in northeast Scotland, UK. Despite the potential for long‐distance dispersal in grouse, and a semicontinuous habitat, significant population divergence was observed (mean R ST = 0.153; P P

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Activity‐Based Environmental Inventory Allocation - Julie Ann Stuart; Laura J. Turbini; Jane C. Ammons (Journal of Industrial Ecology, 1998)
Summary This article presents a generic method to assist product and process designers in measuring resource use and environmental discharges based on the relationships between process flow inputs and outputs and their activity levels. It combines activity‐based costing from conventional accounting with life‐cycle inventories. The method is demonstrated on four electronic assembly product and process designs. The demonstration exhibits the disaggregation and allocation of costs and effluents from various manufacturing operations. This activity‐based environmental allocation approach may be integrated with inventory analysis‐the first step in full and streamlined life‐cycle assessments, design for environment evaluation methods, environmental management activities, and new production planning models that consider environmental impacts.

Use of miniature radio-transmitters to track the movements of dace, Leuciscus leuciscus (L.) in the River Frome, Dorset - Stuart Clough; William R. C. Beaumont (Hydrobiologia, 1998)

Does Lepidopteran Larval Crypsis Extend into the Ultraviolet? - Stuart C. Church; Andrew T. D. Bennett; Innes C. Cuthill; Sarah Hunt; Nathan S. Hart; Julian C. Partridge (The Science of Nature, 1998)

Characterization of two class I genes from the H2-M region: evidence for a new subfamily - S. R. Arepalli; Elsy P. Jones; T. Kevin Howcroft; Irene Carlo; C.-R. Wang; K. Fischer Lindahl; Dinah S. Singer; Stuart Rudikoff (Immunogenetics, 1998)

Measuring Time in the Greenhouse; An Editorial Essay - Brian C. O'neill; Michael Oppenheimer; Stuart R. Gaffin (Climatic Change, 1997)

Measurement of PAN in the Polluted Boundary Layer and Free Troposphere Using a Luminol-NO2 Detector Combined with a Thermal Converter - Chloe Nikitas; Kevin C. Clemitshaw; David E. Oram; Stuart a. Penkett (Journal of Atmospheric Chemistry, 1997)

Does prey dispersion affect frequency-dependent predation by wild birds? - Stuart C. Church; Michael Jowers; John A. Allen (Oecologia, 1997)

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)

Executive function and uptake of 99m Tcexametazime shown by single photon emission tomography after oral idazoxan in probable Alzheimer-type dementia - Guy M. Goodwin; Stuart C. Conway; Helene Peyro-Saint-Paul; Mike F. Glabus; Ronan E. O'Carroll; Klaus P. Ebmeier (Psychopharmacology, 1997)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

A Study of Iron Acquisition Mechanisms of Legionella pneumophila Grown in Chemostat Culture - Brian W. James; W. Stuart Mauchline; P. Julian Dennis; C. William Keevil (Current Microbiology, 1997)

Identification of an assimilatory nitrate reductase in mutants of Paracoccus denitrificans GB17 deficient in nitrate respiration - Heather J. Sears; Phillip J. Little; D. J. Richardson; B. C. Berks; Stephen Spiro; Stuart J. Ferguson (Archives of Microbiology, 1997)

The selective advantages of cannibalism in a Neotropical mosquito - Stuart C. Church; T. N. Sherratt (Behavioral Ecology and Sociobiology, 1996)

Comparison of sensors and techniques for crop yield mapping - Stuart J. Birrell; Kenneth A. Sudduth; Steven C. Borgelt (Computers and Electronics in Agriculture, 1996)

The relative contribution of individual polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-p-furans (PCDFs) to toxic equivalent values derived for bulked human adipose tissue samples from Wales, United Kingdom - Raquel Duarte-Davidson; Stuart J. Harrad; Susan Allen; Andrew S. Sewart; Kevin C. Jones (Archives of Environmental Contamination and Toxicology, 1993)

Evidence of chaotic dynamics underlying the human alpha-rhythm electroencephalogram - A. C. K. Soong; C. I. J. M. Stuart (Biological Cybernetics, 1989)

Avoidance behavior of juvenile striped bass,Morone saxatilis, subjected to simultaneous chlorine and elevated temperature conditions - Lenwood W. Hall; Stuart L. Margrey; Dennis T. Burton; William C. Graves (Archives of Environmental Contamination and Toxicology, 1983)

Isolation of parafluorophenylalanine-resistant mutants from HeLa cell cultures - Lester K. C. Yim; W. Dorsey Stuart (Biochemical Genetics, 1983)

Assignment of histidase-regulating locus to chromosome 10 of the mouse - Stuart M. Arfin; William C. Hanford; Benjamin A. Taylor (Biochemical Genetics, 1979)

Humoral and secretory antibody responses to immunization with low and high dosage split influenza virus vaccine - F. L. Ruben; C. W. Potter; C. H. Stuart-Harris (Archives of Virology, 1975)

Electron microscopic visualization of intranuclear virus-like bodies in epithelial cells infected with poliomyelitis virus - Helmut Ruska; Donald C. Stuart; Johan Winsser (Archives of Virology, 1956)

Complement fixing antigens of herpes simplex virus - D. Balducci; D. A. J. Tyrrell; C. H. Stuart-Harris (Archives of Virology, 1956)

Report of Potato Variety Nomenclature Committee - P. M. Lombard; E. V. Hardenburg; C. H. Metzger; J. C. Miller; William Stuart (American Journal of Potato Research, 1942)

Report of committee on nomenclature - C. F. Clark; E. V. Hardenburg; C. H. Metzger; J. C. Miller; Wm. Stuart (American Journal of Potato Research, 1941)

Report of committee on nomenclature - C. F. Clark; E. V. Hardenburg; C. H. Metzger; J. C. Miller; Wm. Stuart (American Journal of Potato Research, 1940)

Sun injury to cut potato seed - W. C. Edmundson; C. F. Clark; C. H. Metzger; J. C. Miller; Wm Stuart; L. C. Young (American Journal of Potato Research, 1939)

Review of literature - E. V. Hardenburg; W. M. Stuart; C. H. Metsger; W. B. Ward (American Journal of Potato Research, 1934)

The Katahdin potato; A new variety - C. P. Clark; William Stuart; F. J. Stevenson (American Journal of Potato Research, 1931)

Notes - E. V. Hardenburg; J. T.; M. B. Chalker; F. M. Harrington; H. C. M; W. P. Kirkwood; A. G. Tolaas; W. Stuart (American Journal of Potato Research, 1930)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Seed certification in british columbia - S. S. Phillips; E. A. Stokdyk; W. Stuart; H. C. Moore (American Journal of Potato Research, 1926)

Notes on recent literature - W. Stuart; H. M. Steece; Walter M. Peacock; C. F. Clark (American Journal of Potato Research, 1926)

Physiological and storage problems number - H. S. Yohe; Wm. Stuart; C. O. Appleman; John Bushnell; Julian A. Dimock; J. T. Rosa; Earl S. Johnston; E. P. Miller; Freeman Weiss (American Journal of Potato Research, 1925)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Notes on recent literature - W. Stuart; Walter M. Peacock; E. V. Hardenburg; F. Weiss; Walter M. Peacock; C. O. Appleman (American Journal of Potato Research, 1925)

A large potato yield - James C. Knollin; W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - C. F. Clark; W. Stuart (American Journal of Potato Research, 1924)

Potato notes - R. C. Zuckerman; W. Stuart; J. Tucker (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; C. F. Clark (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - W. Stuart; W. H. Martin; Glenn Carter; C. R. Inglee; H. H. Zimmerly (American Journal of Potato Research, 1924)

Potato notes - C. Tice; W. C. Edmundson; W. Stuart; Seymour Bridge; Glen Carter; A. G. Allen; Daniel Dean; H. H. Zimmerly; J. O. Milward (American Journal of Potato Research, 1924)

Potato notes - W. C. Edmundson; W. Stuart; J. C. Crissey; E. V. Hardenburg; W. Stuart (American Journal of Potato Research, 1924)

Notes on recent literature - C. F. Clark; W. Stuart; W. P. Hartman; W. D. Hurd; W. M. Peacock; H. M. Steece (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; W. M. Peacock; W. S. Baird; W. Saxby Blair; R. H. Helmer; W. H. Hicks; W. R. Leslie; B. F. Lutman; H. H. Mann; S. D. Nagpurkar; G. S. Kulkarni; R. S. Kasargode; et al. (American Journal of Potato Research, 1924)

Notes on recent literatur - W. Stuart; W. H. M.; C. F. Clark; W. Stuart; Donald Folsom (American Journal of Potato Research, 1923)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)

Potato notes - Lou D. Sweet; W. Stuart; E. V. Hardenburg; H. C. Moore; W. H. Martin (American Journal of Potato Research, 1923)

Notes on recent literature - C. F. Clark; W. Stuart (American Journal of Potato Research, 1923)